Supplementation of IVM media with equine follicular fluid of large follicles increases blastocyst yield in equine ICSI programs - Luciana Ribeiro Peixoto; Marcos Antônio Gonçalves; José Henrique Fortes Pontes; Perla Dagher Cassoli Fleury; Gustavo Pulzatto Merlini; Thiago Alexandre Robilotta de Oliveira; Victoria Martins Braghetto Barillari; Cláudia Barbosa Fernandes; José Buratini; Vilceu Bordignon; Felipe Perecin (Theriogenology, 2026)

Normalizing eye-tracking metrics: Correcting area bias in visual attention studies - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Jéssica Sousa Guimarães; André Pimenta Freire; Cleiton Antonio Nunes; Ana Carla Marques Pinheiro (Food Quality and Preference, 2026)

Long-term no-till cropping systems enhance nutrient balance and use efficiency while increasing grain yields under tropical conditions - Carlos Alexandre Costa Crusciol; João Henrique dos Santos Ferreira; José Roberto Portugal; Juliano Carlos Calonego; Gustavo Spadotti Amaral Castro; Jayme Ferrari Neto; Katiuça Sueko Tanaka; Letusa Momesso; João Paulo Gonsiorkiewicz Rigon; Romulo Pisa Lollato; Ciro Antonio Rosolem (Soil and Tillage Research, 2026)

Formation and geological significance of carbonate firmgrounds and hardgrounds on the Rio Grande Rise (South Atlantic) - Alexandre Henrique Ferraz; Rafael Oliveira Silva; Pedro Walfir Martins e Souza Neto; Carina Ulsen; Lucy Gomes Sant'Anna; Paulo César Fonseca Giannini; Eugenio Pires Frazão; Victor Hugo Rocha Lopes; Luigi Jovane; Bramley J. Murton; Christian Millo (Sedimentary Geology, 2026)

The Brazilian soil total available water (TAW) acquired by remote sensing and machine learning techniques - Letícia Guadagnin Vogel; Fellipe Alcantara de Oliveira Mello; José Alexandre Melo Demattê; Quirijn de Jong van Lier; Jorge Tadeu Fim Rosas; Leonardo Inforsato; Merilyn Taynara Accorsi Amorim; Nícolas Augusto Rosin; Michele Duarte de Menezes; Marcelo Henrique Procópio Pelegrino; Danilo Cesar de Mello; Renan Falcioni (CATENA, 2026)

Topography- and depth-driven variability of β-glucosidase activity in Amazonian Forest soils (Brazil): A machine learning and structural equation modeling approach - Gizachew Ayalew Tiruneh; Ciro Abbud Righi; Jefferson Lordello Polizel; Vinicius Gonçalves; Carlos Rodrigues Pereira; Fernando Dini Andreote; Rafael Lima Oliveira; Jean Jesus Macedo Novais; Marcelo Henrique Procópio Pelegrino; Jose Alexandre Melo Dematte; Marcelino Carneiro Guedes; Ranjith P. Udawatta (CATENA, 2026)

Living with an apex predator: what do hair glucocorticoids tell us about red fox physiology? - Moisés Leal; Jorge Henriques; Alexandre Azevedo; Jella Wauters; Victor Bandeira (Mammal Research, 2026)

Cover crops shape soil microbiome and ecological interactions in the soybean rhizosphere under long-term no-till - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Nariane de Andrade; Rafael Lima Oliveira; Victor Lucas Vieira Prudêncio Araújo; Felipe Martins do Rêgo Barros; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Soil and Tillage Research, 2026)

Land-use impacts on a soil ecosystem services index in the Brazilian Atlantic Forest biome - Maria Cecília Vieira Totti; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Ricardo de Oliveira Bordonal; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Adriana Marcela Silva-Olaya; Andrés Olaya Montes; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2026)

Cover crops legacy modulates soybean rhizosphere microbiome across phenological stages - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Rafael Lima Oliveira; Nariane de Andrade; Danilo Ferreira da Silva; Mísia Souza Vieira; Victor Lucas Vieira Prudêncio Araújo; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Applied Soil Ecology, 2026)

Integrative cytogenetic and molecular analyses in Hypostomus sertanejo reveal the lowest diploid number in the genus (Siluriformes: Loricariidae) - Daniela Rodrigues; Ligia Carla Balini; Bárbara Scorsim; Cláudio Henrique Zawadzki; Alessandra Valéria de Oliveira; Marcos Otávio Ribeiro; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes; Eliane Papa Ambrosio-Albuquerque; Luciana Andreia Borin-Carvalho (Biologia, 2026)
Expanding integrative cytogenetic and molecular analyses is essential for understanding the evolutionary dynamics of chromosome number variation in fishes. This study presents the first cytogenetic characterization of Hypostomus sertanejo , an endemic species native to the semi-arid Jaguaribe River basin in Northeastern Brazil. Cytogenetic analysis revealed a diploid number of 2n = 52, which is the lowest documented for the genus, with a karyotype composed of 22m + 8sm + 16st + 6a and a fundamental number of 98. This value aligns with the ancestral diploid number suggested for the tribe Hypostomini. Fluorescence in situ hybridization identified a single 18S rDNA site coinciding with the nucleolar organizer region, while 5S rDNA was localized to an interstitial position on a unique chromosome pair. Molecular analysis based on COI gene confirmed the identity of H. sertanejo and its distinction from closely related species. These results reveal a distinctive evolutionary trajectory for H. sertanejo relative to other Hypostomus species and highlight the importance of integrating data to elucidate diversification patterns in endemic fish lineages.

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Policy roadmap for governing new oil frontiers under environmental constraints: Lessons from Brazil's Foz do Amazonas basin - Camila Ludovique Callegari; Julia Paletta; Ana Carolina Oliveira Fiorini; Rebecca Draeger; Pedro Henrique Batista de Barros; Renan Medeiros; Alexandre Szklo (Energy Policy, 2026)

Seafloor erosional processes within the Rio Grande Rise: Integrated results from past scientific expeditions - Gabriel Tagliaro; Alexandre Henrique Ferraz; Raylla Souza Silva; Christian Millo; Renata Regina Constantino; Bramley J. Murton; Luigi Jovane (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Diagnosis of acetaminophen and codeine poisoning in a dog using earwax analysis by headspace gas chromatography-mass spectrometry (HS/GC-MS) - Monica Chacon de Vicente; Alexandre Có Mangoni Barros; Gabriela Scarpin de Souza; Lais di Pauli Taborda Prado; João Marcos Gonçalves Barbosa; Rayanne Henrique Santana da Silva; Leidiane de Souza Gomes; Danieli Brolo Martins; Nelson Roberto Antoniosi Filho; Ana Flávia Machado Botelho (Veterinary Research Communications, 2026)
Poisoning of companion animals resulting from exposure to analgesics intended for human use is a frequent and clinically relevant problem in veterinary practice, usually associated with administration without professional supervision. This can induce severe systemic toxicity. Diagnostic confirmation can be particularly challenging in cases presenting with nonspecific clinical signs or when conventional biological samples are unavailable. This case report describes the innovative use of earwax as a non-invasive biological matrix for toxicological confirmation in veterinary medicine. A 9-year-old male mixed-breed dog was admitted following a traumatic accident and subsequent administration by its owner of a human medication containing acetaminophen and codeine. Clinical evaluation revealed lethargy, hypersalivation, hyporexia, dehydration, and neurological abnormalities. Laboratory findings demonstrated neutrophilic leukocytosis and marked increases in hepatic enzyme activities, consistent with acute hepatocellular injury. Toxicological investigation using headspace gas chromatography–mass spectrometry detected acetaminophen-related signatures in an earwax sample, supporting suspected exposure to the drug. Intensive treatment was promptly initiated and included fluid therapy, antidotal treatment with N-acetylcysteine, opioid antagonism, analgesia, and supportive care. The patient showed progressive clinical improvement, with complete resolution of clinical signs and full recovery. This case highlights the significant risks of administering human medications to companion animals and underscores the need to improve owner awareness of self-medication practices. Furthermore, it demonstrates the diagnostic potential of earwax as a non-invasive biological matrix for toxicological confirmation, expanding the range of complementary diagnostic tools available for veterinary toxicology and supporting improved clinical decision-making in cases of suspected pharmaceutical intoxication.

Biochemical characterisation of a new thermotolerant L-asparaginase produced by Cunninghamella echinulata PA3S12MM isolated from the Atlantic Forest - Simone Von Groll; Leticia Claudia da Silva; Pedro Henrique Nascimento Souza; Wállison Justino da Silva; Thaís Duarte Bifano; José Luis da Conceição Silva; Rita de Cássia Garcia Simão; Simão; Marina Kimiko Kadowaki; Alexandre Maller (Archives of Microbiology, 2026)
L -asparaginase is an amidohydrolase enzyme that catalyses the hydrolysis of L-asparagine into L-aspartic acid and ammonia. This enzyme has significant biotechnological applications, functioning as an antineoplastic agent in the pharmaceutical industry and as a tool for reducing acrylamide formation in the food industry. This study aimed to identify a filamentous fungus strain capable of synthesizing a new L -asparaginase and to perform its biochemical characterisation. Among the fungal isolates screened using plate assays and submerged fermentation, Cunninghamella echinulata strain PA3S12MM was identified as a promising L -asparaginase producer. The highest enzymatic induction was achieved using 5% (w/v) glucose as the carbon source and 0.4% (w/v) chicken feather as an agro-industrial nitrogen source, under incubation for 120 h. The enzyme exhibited an apparent K m app of 0.011 mmol L⁻¹ and a V max app of 126.5 mmol L⁻¹ min⁻¹ for the hydrolysis of L-asparagine. Partial purification revealed that the enzyme displayed optimal activity at pH 7.0 and a temperature of 85 °C. In terms of substrate specificity, the enzyme demonstrated 100% relative activity toward L-asparagine and 32.9% toward L-glutamine. Enzymatic activity was enhanced by β-mercaptoethanol but inhibited by Mn²⁺, L-cysteine, and dithiothreitol (DTT). These findings suggest that C. echinulata PA3S12MM is a promising candidate for large-scale biotechnological production of a new fungal L -asparaginase, with biochemical indicators of potential for applications in both pharmaceutical and food industries.

Elemental homeostasis and soil microbiota of forage grasses under drought and irrigation - Cíntia Cármen de Faria Melo; Danilo Silva Amaral; Carlos Henrique Barbosa Santos; Everlon Cid Rigobelo; Mara Cristina Pessôa da Cruz; Renato de Mello Prado; Alexandre Barcellos Dalri; Luís César Dias Drumond (Plant and Soil, 2026)
Aims Perennial forage systems in tropical regions are predominantly dryland; however, increasing drought frequency associated with climate change has accelerated the adoption of irrigation. Selecting forage species capable of maintaining elemental balance and favorable plant-soil interactions is essential to sustain productivity. This study evaluated the drought tolerance of Mavuno and Zuri grasses under tropical field conditions, focusing on their responses to subsurface drip irrigation, plant carbon (C), nitrogen (N) and phosphorus (P) stoichiometry, and soil microbial dynamics. Methods A field experiment was conducted under dryland and irrigated conditions, assessing forage biomass production, plant water status, leaf C, N, and P concentrations, and indicators of soil microbial activity and composition in rhizosphere and non-rhizosphere compartments. Results Under dryland conditions, both grasses exhibited reductions in biomass production; however, Mavuno maintained greater elemental homeostasis and higher soil microbial activity, suggesting greater tolerance to seasonal water deficit. Irrigation restored plant water status, improved C:N:P ratios, and increased the abundance of key microbial groups, including sporulating bacteria, yeasts, and actinomycetes. Forage yield increased by approximately 10 Mg ha⁻ 1 of dry matter under irrigation for both species. Under irrigated conditions, Zuri grass was associated with higher microbial biomass C and total soil organic C, indicating enhanced soil C inputs. Conclusion These findings demonstrate species-specific responses to water availability and show that irrigation modulates plant nutrient stoichiometry and soil microbial processes. The choice of forage species with stable elemental composition and favorable plant-soil interactions plays a key role in sustaining productivity.

Elicitation with Proline Enhancing Chlorophyll Fluorescence, Antioxidant Metabolism to Scavenge ROS, and Osmolytes Accumulation in Beets - Grazielli Medeiros da Silva; Adeline de Souza; Danilo André Ramalho de Campos; Alexandre Esteves Dias Filho; Alessandra Maria dos Santos; Angélica Maria Lourenção; Pedro Henrique Gorni (Journal of Plant Growth Regulation, 2026)

Seasonal Expansion and Spatial Concentration in Arctic Shipping: A Data-Driven Analysis Using the Arctic Traffic Intensity Framework - Pedro Coelho Terossi; Yuri Alexandre Meyer; Rafael Henrique de Oliveira (Journal of Marine Science and Engineering, 2026)
The rapid cryospheric transformation of the Arctic presents complex challenges for global supply chains, necessitating data-driven decision-making frameworks to optimize route planning and resource allocation. Standard aggregate statistics fail to capture the structural nuances required for operational research models in this evolving landscape. This study analyzes the spatiotemporal dynamics of Arctic navigation intensity to determine the extent of the operational window expansion and the spatial displacement of shipping routes. We deployed the Arctic Traffic Intensity Framework (ATIF) to generate a high-resolution spatiotemporal dataset spanning 2012–2024. To address variance instability and inform strategic forecasting, a log-linear regression model was applied to calculate the Annual Percentage Change, allowing for a dual analysis of absolute linear trends (volume) versus relative growth (proportional intensity) across heterogeneous baselines. A bilateral expansion of the high-intensity window to nearly five months (June–October) was observed, driven by earlier spring break-up and delayed autumn freeze-up. Spatially, the geometric navigational centroid has shifted southwestward, highlighting a concentration of activity in the Barents and Kara Seas rather than a uniform Transpolar dispersion. It can be concluded that the Arctic shipping system has transitioned from a seasonally restricted frontier to a standardized resource extraction corridor. However, the traffic is heavily clustered in the western sector, creating high-density logistic bottlenecks rather than a homogenized international transit route.

Feeding habits of the franciscana dolphin Pontoporia blainvillei (Gervais & d’Orbigny, 1844) in Ilha Grande Bay, southeastern Brazil - Nerelle Vital; Emi Brinatti Guari; Pedro Henrique de Oliveira Teixeira; Elitieri Batista Santos Neto; Rafael Ramos de Carvalho; Haydée Andrade Cunha; Tatiana Lemos Bisi; José Lailson Brito Junior; Alexandre de Freitas Azevedo (Regional Studies in Marine Science, 2026)

Effects of extreme hydrological disturbances on the resilience, resistance, and functional redundancy of fish assemblages in a subtropical estuary - Erika Belarmino; Alice Marlene Grimm; Henrique Cabral; Alexandre Miranda Garcia (Marine Environmental Research, 2026)

Physiological and metabolic responses of cobia (Rachycentron canadum) juveniles fed fish oil-free diets with different LC-PUFA/C18 PUFA ratios - Sabrina Vitória Ferreira da Costa; Bruno Cavalheiro Araújo; Renata Guimarães Moreira; Renato Massaaki Honji; Julia Sousa Siqueira; Paulo Henrique de Mello; Alexandre Wagner Silva Hilsdorf; Micheli Zaminhan-Hassemer (Animal Feed Science and Technology, 2026)

Interplay Between River Formation and Historical Climatic Changes Drove Diversification of the Thamnomanes caesius and T. schistogynus (Passeriformes, Thamnophilidae) Species Complex Across Amazonian and Atlantic Forests - Henrique Batalha‐Filho; Tibério César Tortola Burlamaqui; Martin Irestedt; Per G. P. Ericson; Jon Fjeldså; Cristina Yumi Miyaki; Alexandre Aleixo (Zoologica Scripta, 2026)
The Amazon and Atlantic forests harbour immense biodiversity shaped by complex evolutionary history with diverse processes leading to species build‐up. We investigated the Cinereous Antshrike species complex ( Thamnomanes caesius and T. schistogynus ) to disentangle the relative contributions of riverine barriers and historical climatic fluctuations to diversification, using large specimen sampling across their entire distribution and a multilocus dataset. Our results revealed hidden genetic diversity, with 13 geographically structured phylogroups largely concordant with Amazonian interfluves and areas of endemism. Species delimitation analyses supported eight of these lineages as independently evolving units, unveiling cryptic diversity within T. caesius . Divergence time estimates indicate that diversification took place during the Pliocene to Late Pleistocene, with signatures of demographic expansion consistent with climate‐driven range dynamics. Our findings underscore a strong association between phylogroups and major river systems, revealing their role as primary drivers of lineage diversification, later modulated by demographic shifts associated with climatic oscillations. Our findings highlight an interplay between geomorphological and climatic factors in shaping avian diversity across the Amazon basin, while also pointing to underestimated taxonomic richness within the Thamnomanes caesius /schistogynus species complex.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Worldwide diversity and ecology of mangrove fungi: a systematic review of ITS metabarcoding studies and a quantitative, integrative analysis of raw sequence data - Isabela Maria Agustini da Silveira Bastos; Mariana Santos Cardoso; Marcele Laux; Rafael Rios Ribeiro; Glen Jasper Yupanqui García; Paloma Araujo Bahia; Paulo Miguel Vieira de Sousa; Bella Giselly Torres Alves; Diogo Henrique Costa de Rezende; Alexandre Soares Rosado; Jadson D.P. Bezerra; Melissa Fontes Landell; et al. (World Journal of Microbiology and Biotechnology, 2026)

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

Effect of zinc oxide nanoparticle supplementation in Santa Inês ewes during the transition period - Willinton Hernan Pinchao Pinchao; Henrique de Brito Guedes; Carolina Rodriguez Jimenez; Gabriele Rossini Moreira; Murilo Antônio Fernandes; Bruna Gonçalves Santos Costa; Luciana Morita Katiki; Elisabete Aparecida de Nadai Fernandes; Mateus Oliveira Mena; César Cristiano Bassetto; Ana Cláudia Alexandre de Albuquerque; Alessandro Francisco Talamini do Amarante; et al. (Tropical Animal Health and Production, 2026)
Zinc oxide nanoparticles (N-ZnO) represent a promising alternative for zinc (Zn) supplementation, since their reduced size provides greater bioavailability and better integration into the body. Furthermore, this characteristic becomes particularly relevant during periods of increased metabolic stress, such as the transition phase. Thus, the objective was to evaluate the effects of N-ZnO supplementation in Santa Inês sheep during the peripartum period. Thirty-three ewes with an average body weight of 43.3 ± 2.05 kg were, distributed into three experimental groups: control group (CON), without supplementation, receiving only Cynodon spp. hay; and groups supplemented with 300 mg/animal/day of N-ZnO (40 nm) and zinc oxide microparticles (M-ZnO). The supplementation was administered orally in capsules daily from late pregnancy until weaning. The results showed no significant differences ( P > 0.05) in body weight, egg count per gram of feces (EPG), and in most of the hematological, biochemical, and immunological parameters evaluated. However, differences ( P < 0.05) were observed in monocyte counts and albumin levels, with higher means in the N-ZnO group, showing differences compared with the M-ZnO group, while the CON group maintained intermediate values. The N-ZnO group showed differences compared to the M-ZnO group, while the CON group maintained intermediate values. Regarding antioxidant activity, a significant effect ( P < 0.05) was observed on the enzymes Superoxidase dismutase (SOD), Glutathione peroxidase (GPx), Catalase (Cat), and on the total antioxidant status (ORAC) of the sheep supplemented with N-ZnO. It is concluded that N-ZnO supplementation improved the antioxidant response, with no signs of intoxication, using a dose of 300 mg during the period of greatest oxidative stress.

Optimizing soybean breeding: High-throughput phenotyping for stink bug resistance and high yields - Maiara de Oliveira; Alexandre Hild Aono; Patricia Braga; Adriano Abreu Moreira; Fernanda Smaniotto Campion; Felipe Augusto Krause; Fernando Henrique Iost Filho; Juliano de Bastos Pazini; Pedro Takao Yamamoto; José Baldin Pinheiro (Precision Agriculture, 2026)
Background: The stink bug complex is one of the most damaging pests of soybean, reducing yield and seed quality. Genetic resistance remains the most sustainable and effective management strategy, but its quantitative inheritance and labor-intensive field phenotyping make its implementation in breeding programs challenging. Objective: This study explored high-throughput phenotyping (HTP) using unmanned aerial vehicles (UAVs) equipped with RGB cameras to evaluate a soybean population and the potential of phenotyping to stink bug resistance by correlating image-derived features and machine learning (ML) models. Methods: A population of 304 soybean lines was evaluated in alpha-lattice design trials across two seasons under natural infestations. Five resistance-related traits, grain yield (GY), healthy seed weight (HSW), number of days to maturity (NDM), tolerance (TOL), and leaf retention (LR), were manually scored and linked to UAV-derived vegetation indices (VIs) and texture indices (TIs). Three ML models (AdaBoost, SVM, MLP) were tested to predict these traits from aerial features. Results: Results showed that VIs, particularly Visible Atmospherically Resistant Index at the 25th percentile (VARI_P25), were consistently associated with resistance-related traits, while decision tree analysis highlighted TIs at 45° and 135° as complementary sources of structural information. Prediction ability was highest for GY, HSW, and NDM, especially in flights near flowering and maturity, but remained low for TOL and LR. Integrating multiple flights modestly improved accuracy, whereas cross-season predictions were unreliable. Nonetheless, indices such as VARI_P25 provided useful cross-season correlations for HSW and TOL, enabling early screening of less promising lines. Conclusion: This pioneering study demonstrates that UAV–ML pipelines can capture genetic signals of stink bug resistance in soybean, despite environmental complexity. These findings open new avenues for resistance phenotyping, supporting more efficient breeding strategies and accelerating genetic gains in soybean improvement.

Molecular epidemiological surveillance of circovirus in avian and mammalian species on the Brazilian coast - Ana Julia Chaves Gomes; Yasmin Luisa Neves Lemes Garcia; Dayla Bott Geraldini; Camila Domit; Fábio Henrique de Lima; João Pessoa Araújo; Juliana Schons Gularte; Micheli Filippi; Vyctoria Malayhka de Abreu Góes Pereira; Meriane Demoliner; Alexandre Sita; Fernando Rosado Spilki; et al. (Archives of Virology, 2026)
Circoviruses (CVs) infect diverse mammals, birds, and freshwater fish and are linked to diseases causing major economic losses. Despite being well studied in psittacines, their circulation in other avian groups and mammals is poorly understood. We conducted molecular surveillance of CVs in migratory birds and mammals along the Paraná coast, southern Brazil. Sterna hirundinacea specimen tested positive by Nested-PCR for GullCV. In the GullCV-infected bird, histopathology revealed nonspecific lesions, including marked splenic lymphoid atrophy, cachexia-related changes, acute tubular necrosis, and generalized congestion. Sanger sequencing revealed 83% nucleotide identity with CV sequences previously reported in gulls from the United States, which was consistent with results obtained by NGS and Rep-based phylogenetic analysis. These findings contribute to the understanding of CV diversity, distribution, and host range.

Influence of coral reef morphology on wave climate and sea-level rise projections along a reef-protected beach in Northeast Brazil - Larissa Fernandes de Lavor; Maria Cecilia Silva Souza; Karina Massei; Alexandre dos Santos Souza; Valdir do Amaral Vaz Manso; Virgínio Henrique de Miranda Lopes Neumann; Pedro Costa Guedes Vianna; Christianne Maria da Silva Moura; Nadja Cecília de Freitas Silva; Richarde Marques da Silva; Rogério dos Santos Ferreira; Jefferson da Costa Silva; et al. (Regional Studies in Marine Science, 2026)

Environmental gradients shape fish assemblages across estuarine-coastal ecosystems on the eastern Brazilian coast - Rafael L. Oliveira; Germano Henrique Costa Barrilli; Mauricio Hostim-Silva; Ronaldo R. Oliveira-Filho; Helen A. Pichler; André P. Cattani; Ryan Andrades; Ciro C. Vilar; Ana C. Martins; Valéria M. Lemos; Alexandre M. Garcia; Henry L. Spach; et al. (Marine Environmental Research, 2026)

Intensified tropical pasture-based beef cattle production systems and their effects on carcass traits, meat quality and methane emissions from Nellore steers - Gabriele Voltareli da Silva; Rolando Pasquini Neto; Mariana Nunes Vieira de Melo; Luiza Budasz de Andrade; Althieres José Furtado; Ester Costa Fabricio; Analisa Vasques Bertoloni; Annelise Aila Gomes Lobo; Flavio Perna Junior; Sérgio Raposo de Medeiros; Alexandre Berndt; Renata Tieko Nassu; et al. (Livestock Science, 2026)

Balancing torque, efficiency, and emissions: A framework for engine optimization using modern metaheuristics - Marcos Henrique Carvalho Silva; André Vinícius Oliveira Maggio; Paulo Alexandre Pizará Hayashida; Armando Antônio Maria Laganá; Bruno Silva Pereira; João Francisco Justo (Journal of Environmental Management, 2026)

Redox Dynamics Modulate Vascular Tissue Reconnection and Early Growth after Grafting in Pyrus andCydonia - Evaldo Tadeu de Melo; Rafael Pio; Daniela da Hora Farias; Alexandre Dias da Silva; Evaristo Mauro de Castro; Carlos Henrique Milagres Ribeiro (Journal of Plant Growth Regulation, 2026)
Graft success depends on coordinated vascular tissue regeneration to restore scion growth. Reactive oxygen species (ROS), particularly hydrogen peroxide (H₂O₂), are involved in wound signalling, yet their role in controlling intergeneric graft compatibility remains unclear. This study evaluated early growth, redox metabolism and vascular reconnection in intergeneric grafts between quince ( Cydonia oblonga ) and pear ( Pyrus spp.). A completely randomised 2 × 8 factorial scheme was adopted, comprising two rootstocks ( Pyrus calleryana and Chaenomeles sinensis ) and eight scion genotypes. Sprouting percentage, shoot length and diameter, hydrogen peroxide (H₂O₂) concentration, malondialdehyde (MDA) content and anatomical reconnection were assessed up to 120 days after grafting. Compatible combination exhibited markedly higher sprouting and shoot growth; for instance, ‘Triunfo’ reached 100% sprouting on P. calleryana , whereas P. calleryana on C. sinensis failed completely (0%), and C. sinensis on P. calleryana showed only about 10% sprouting. Callus formation was detected as early as 5 days after grafting (DAG), and continuous vascular connections were established by 25 DAG in compatible grafts, while incompatible combinations developed necrotic barriers at the graft interface. H₂O₂ concentration in the graft region ranged from approximately 261 to 579 nmol g⁻¹ FW and was generally higher in scion tissues, whereas MDA accumulation was greater in rootstocks, reaching up to around 560 µmol MDA g⁻¹ FW. Although single point oxidative markers did not strictly discriminate compatible from incompatible combinations, tissue-specific redox patterns and their timing were consistently associated with the speed of vascular reconnection and early scion growth. These findings demonstrate that ROS function not only as stress markers but also as developmental signals during graft healing, and suggest early vascular reconnection together with scion H₂O₂ and rootstock MDA as promising indicators of graft performance in woody species.

Genotype and year effects on seed and seedling traits of Coffea canephora - Laísa Zanelato Correia; Henrique Duarte Vieira; Rosenilda de Souza; Alexandre Pio Viana; Fábio Luiz Partelli (Euphytica, 2026)
The investigation of genotype behavior under varying conditions is conducted to maximize selection gains in coffee breeding programs, aiming to identify genotypes that sustain good performance across different environments and years. The objective of this study was to estimate the magnitudes of the effects of genotype and year on seed and seedling traits of Coffea canephora . 43 C. canephora genotypes were evaluated for the physical and physiological traits of seeds and seedlings during two crop years (2019 and 2020). Both individual and joint analyses were performed to obtain estimates of genetic parameters and the effects of genotype, year, and genotype × year interaction. Individual analyses identified significant differences ( p ≤ 0.01) among genotypes for all traits in both evaluated years. The year effect was significant for all variables except germination, whereas the interaction significantly impacted all traits. The proportion of simple interactions exceeded that of complex ones for germination speed index (GSI), area, roundness, circumference, and thousand seed weight (TSW). The complex interaction was predominant over simple ones for germination and shoot (SL) and root lengths, reaching 97.79% of the total interaction. Genotypes Bicudo, Penirão e Pirata showed good performed for TSW and SL, with little variation in the averages between the years. Bamburral exhibited average performance and least variation between years. The significant effect of year was attributed to the genotype effect rather than climatic differences. Therefore, the selection of superior C. canephora materials for seed traits should consider the average performance of the genotypes across different years.

Rare-Earth Elements (REE) and Mercury in the Historically Important Miguel Burnier Manganese-Ore District, Quadrilátero Ferrífero of Minas Gerais, Brazil - Tiago Henrique DeFerreira; Alexandre Raphael Cabral; Francisco Javier Rios; Lucas Eustáquio Dias Amorim (Journal of Earth Science, 2026)

L-asparaginase by filamentous fungi and yeasts from lichens and soils across maritime Antarctic islands - Averlane Vieira da Silva; Bárbara Emanuelle Fernandes Ferro; Vanessa Daiany Vieira Medeiros; Valdilene Canazart dos Santos; Maria Nicolle Pereira da Silva; Cledna Kaline dos Santos Duarte; Aline Cavalcanti de Queiroz; Magna Suzana Alexandre Moreira; Luiz Henrique Rosa; Alysson Wagner Fernandes Duarte (Extremophiles, 2026)

Morphological characterization and distribution of antennal sensilla on Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) - Elmadã Pereira Gonzaga; Camila Alexandre Cavalcante de Almeida; Lucas Teles Bezerra; Maclauds Nathan Feliciano Salmento; Fernanda da Silva Gonçalves; Henrique Fonseca Goulart; Antônio Euzébio Goulart Santana; Johnnatan Duarte de Freitas; Mariana Oliveira Breda (Zoologischer Anzeiger, 2026)

Readily available water supply across soil variability in a center-pivot irrigated soybean field using the least limiting water range approach - Igor Alexandre de Souza; Dorotéo de Abreu; Alceu Linares Pádua Junior; Sérgio Henrique Godinho Silva; Bruno Montoani Silva (Geoderma Regional, 2026)

Agro-industrial residues from baru (Dipteryx alata Vogel) for the development of active and nanostructured biodegradable films - Gracieli de Miranda Monteiro; Rafael Carvalho do Lago; Luíz Guilherme Malaquias da Silva; Carlos Alexandre Rocha da Costa; Gustavo Henrique Denzin Tonoli; Marina Rocha Komeroski; Alessandro de Oliveira Rios; Elisângela Elena Nunes Carvalho; Eduardo Valério de Barros Vilas Boas (Food Packaging and Shelf Life, 2026)

So close and unnoted: a new host plant of Cerataphis brasiliensis (Hempel) (Hemiptera: Aphididae) - Nyeppson de Sousa Soares; Alexandre Santos Araújo; Leonardo Souza Duarte; Frederico Hickmann; Thiago Henrique dos Reis Pádua; Mateus Souza Lima Aurélio; Sinval Silveira Neto; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
Cerataphis brasiliensis (Hempel) (Hemiptera: Aphididae), the palm aphid, is native to Asia and, in several countries, has been associated with some economically important palm trees (Arecaceae). This study aims to document, for the first time, the occurrence of C. brasiliensis on Butia odorata (Barb. Rodr.) Noblick (Arecaceae) in the municipality of Piracicaba, São Paulo State, Brazil. The identity of the specimens was verified through both morphological and molecular analyses, specifically examining the mitochondrial gene cytochrome c oxidase subunit I (COI). The haplotype of the specimen collected on Butia palm tree exhibited over 99% homology with other sequences of C. brasiliensis , thereby confirming the species identity. Observations indicated a clear preference of the aphid for the rachillae and fruits of B. odorata . Additionally, for the first time, a mutualistic interaction between Camponotus crassus Mayr (Hymenoptera: Formicidae) and the palm aphid was documented. Currently, C. brasiliensis is known to associate with species from four botanical families, with a predominant occurrence in Arecaceae throughout South America.

A multidriver assessment of beach litter accumulation rates - Lucio Brabo; Henrique Araújo de Oliveira; Tamyris Pegado; Ryan Andrades; Friedrich Wolfgang Keppeler; Manoela de Araujo Sampaio; Francisco José Mariano Vasconcelos; Alexandre David Dantas; Regina Kátia Saraiva Carneiro; Kelly Ferreira Cottens; Nelson Guillermo Rangel-Buitrago; Tarin Frota Mont'Alverne; et al. (Marine Pollution Bulletin, 2026)

In vivo genotoxicity and water quality assessment reveal urban influences on the Capibaribe River, Northeastern Brazil - Tyago Henrique Alves Saraiva Cipriano; Jaqueline dos Santos Silva Pinheiro Rodrigues; Livia Caroline Alexandre de Araújo; Iago José Santos da Silva; Aleson Aparecido da Silva; Erima Maria de Amorim; Maria Gislaine Pereira; Lizandra Ferraz da Silva; Eduardo Henrique da Silva Melo; Amanda Alves de Araújo; Anadeje Celerino dos Santos Silva; Elvis Joacir De França; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Membrane-targeted photodynamic mechanisms of methylene violet 3RAX in melanoma models - Thais Soares de Oliveira; Mirella Boaro Kobal; André Satoshi Ferreira; Alexandre Mendes de Almeida Junior; Karina Alves Toledo; Sabrina Aléssio Camacho; Pedro Henrique Benites Aoki (Journal of Photochemistry and Photobiology B: Biology, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Determination of soil organic carbon and nutrients by diffuse spectrorradiometry in the Cerrado Mineiro region, Brazil: evaluation of strategies for calibration of hyperspectral models - Everson Cezar; Tatiane Amancio Alberton; Evandro Freire Lemos; Nicole Ghinzelli Vedana; Karym Mayara de Oliveira; Luís Guilherme Teixeira Crusiol; Marlon Rodrigues; Renan Falcioni; Jose Alexandre Melo Demattê; Marcelo Henrique Procópio Pelegrino; Marcos Rafael Nanni (International Journal of Remote Sensing, 2026)

Influence of canopy cover on the diversity of Anastrepha (Diptera: Tephritidae) in an Atlantic forest fragment in Brejo Paraibano, Northeast Brazil - Manoel Cícero de Oliveira Filho; Janderson Batista Rodrigues Alencar; Alexandre Santos Araújo; Nyeppson de Sousa Soares; Lylian Souto Ribeiro; Marcoandre Savaris; Carlos Henrique de Brito (International Journal of Tropical Insect Science, 2026)

Monitoring tailings remobilization after the VALE S.A. Dam failure in Brumadinho: Impacts of extreme floods assessed through remote sensing - Hugo Henrique Cardoso de Salis; Alexandre de Lima Chumbinho; Irla Paula Stopa Rodrigues; Marilia Andrade Fontes (Remote Sensing Applications: Society and Environment, 2026)

Effect of high growth rate in prepubertal age on hormonal and puberty status in crossbred (Angus x Nellore) heifers - Marcos Vinicius de Castro Ferraz Junior; Marcelo Henrique Santos; Gabriela Baggio de Oliveira; Daniel Montanher Polizel; Guilherme de Paula Nogueira; Vinícius Nunes de Gouvêa; Janaina Socolovski Biava; Evandro Maia Ferreira; Nelma Pinheiro Fragata Beltrão; Alexandre Vaz Pires (Tropical Animal Health and Production, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Beach sensitivity to mining tailings index using a morphodynamic variables approach: case study of the Fundão dam failure (Southeast Brazil) - Giseli Modolo Vieira Machado; Maitê Noda-Zanotti; Lucas Bermudes de Castro; Alexandre Burini; Luiz Henrique Sielski; Jacqueline Albino (Regional Studies in Marine Science, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Flood-Fire Interplays in Wetlands: The Rising of an Actionable Field of Study - Geraldo Alves Damasceno-Junior; Alexandre de Matos Martins Pereira; Bambang Hero Saharjo; Sally Archibald; Beibei Zhang; Bibiana Bilbao; Bruno Henrique dos Santos Ferreira; Carol Kagaba Kairumba; Danilo Bandini Ribeiro; David G. Campbell; Denis Mburu Njoroge; Dennis Twinomujuni; et al. (Wetlands, 2025)
Floods and fires are part of the ecological regime in many wetlands, yet their interconnectedness is poorly explored. Climate extremes, such as droughts and heatwaves, are increasing fire frequency and intensity, while changing rainfall patterns make floods more unpredictable. These events shape wetland physiognomy, species composition, and functioning. Different wetlands experience varying fire exposure; seasonally inundated grasslands burn almost annually, whereas tropical forests rarely catch fire. Some wetlands are more resilient to fire, drought, and floods than others. Communities dependent on wetlands possess ecological knowledge that supports adaptation, enhancing ecosystem resilience. Though often studied separately, floods and fires in wetlands are interrelated. In addition to environmental aspects, social, cultural and associated traditional knowledge dimensions must be included in conservation processes for these environments. A holistic understanding is crucial for conservation. Researchers from sixteen countries propose a new field of study on flood-fire interactions to improve wetland management and sustainability.

Putative Antagonistic Effects of Mycorrhiza Waitea circinata Against Colletotrichum falcatum Causing Agent Red Rot in Sugarcane - Marcio Mesquita; João Abrão Batista Gundim; Amanda Abdallah Chaibub; Renato de Carvalho Menezes; Bruna Mendes de Oliveira; Alexandre Siqueira Guedes Coelho; Diogo Henrique Morato de Moraes; Marcos Gomes da Cunha; Leila Garcês de Araújo (Sugar Tech, 2025)

Evaluation of Optimal Timing for Replacement of Self-Propelled Sugar Cane Harvesters - Erick Henrique Romero; Priscila Fernanda Pereira Barbosa; Paulo Alexandre Monteiro de Figueiredo; Sérgio Bispo Ramos; Ronaldo da Silva Viana (Sugar Tech, 2025)

Crop rotation and succession in soybean production systems: cover crop biomass, grain yield and revenue - Leandro Pereira Pacheco; Claudinei Kappes; Andressa Selestina Dalla Côrt; Rayane Gabriel da Silva; Edicarlos Damacena de Souza; Thaís Rodrigues Magalhães Guedes; Laércio Santos Silva; Rafael Felippe Ratke; Fabiano André Petter; João Henrique dos Santos Ferreira; José Roberto Portugal; Ivan David Ferreira Silva; et al. (Plant and Soil, 2025)

Multiomic insights into sucrose accumulation in sugarcane - Alexandre Hild Aono; Ricardo José Gonzaga Pimenta; Jéssica Faversani Diniz; Marishani Marin Carrasco; Guilherme Kenichi Hosaka; Fernando Henrique Correr; Ana Letycia Basso Garcia; Estela Araujo Costa; Alisson Esdras Coutinho; Luciana Rossini Pinto; Marcos Guimarães de Andrade Landell; Mauro Alexandre Xavier; et al. (Plant Molecular Biology, 2025)

Mercury isotopes from ferromanganese rocks fingerprint metal recycling by intracontinental basinal fluids - Alexandre Raphael Cabral; Runsheng Yin; Di Chen; Stephanie Lohmeier; Tiago Henrique DeFerreira; Francisco Javier Rios; Bernd Lehmann (Applied Geochemistry, 2025)

Antibacterial and antibiofilm activity of ruthenium polypyridine complex against Staphylococcus strains - Leonardo Silva de Sousa; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Felipe Diógenes Abreu; Eduardo Henrique Silva Sousa; Idalina Maria Moreira de Carvalho; Débora S. C. M. Castelo-Branco; Mayron Alves de Vasconcelos; Edson Holanda Teixeira (Biofouling, 2025)

Forest fires in Caatinga: Risk modeling and priority areas for prevention - Mariana de Aquino Aragão; Nilton Cesar Fiedler; Alexandre Rosa dos Santos; Tais Rizzo Moreira; Antonio Henrique Cordeiro Ramalho; Robert Gomes; Patrícia Carneiro Souto; Telma Machado de Oliveira Peluzio; Jéferson Luiz Ferrari; Danilo Simões; Leonardo Duarte Biazatti; Fernanda Moura Fonseca Lucas (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Enhanced antimicrobial and antibiofilm activities of ruthenium complexes with fluorine- and bromine-substituted ligands against staphylococcal strains - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Isa Maria Ferreira Azevedo; Tatiane Gomes da Silva; Paula Victoria Soares; Ellen Araújo Malveira; José Marcos da Silveira Carvalho; Débora S. C. M. Castelo-Branco; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2025)

Prospecting the phytochemical and antioxidant effects in vivo and in vitro of the ethanolic and aqueous extracts of the seeds of Geoffroea decorticans burkart (Fabaceae) on the animal model Tenebrio molitor - Ariana Pereira da Silva; Maria Lúcia da Silva Cordeiro; Verônica Giuliani de Queiroz Aquino Martins; Georggia Fatima Silva Naliato; Raquel Cordeiro Theodoro; Carlos Henrique Salvino Gadelha Meneses; Hugo Alexandre Oliveira Rocha; Kátia Castanho Scortecci (Phytochemistry Letters, 2025)

Screening plant extract for biological activity. A work spanning 60° Latitude South - Ivana Barbosa Suffredini; Amanda Leal da Silva Teodoro; Marcelo Henrique Soller Ramada; Sergio Alexandre Frana; Mateus Luís Barradas Paciencia; Jefferson de Souza Silva; Paulo Eduardo Aguiar Saraiva Câmara; Antonio Drauzio Varella (Phytochemistry Letters, 2025)

Malassezia pachydermatis sensitivity to plant extracts from the Brazilian Amazon Rain Forest - Ivana Barbosa Suffredini; Jefferson de Souza Silva; Sergio Alexandre Frana; Karen Cristina Comin Maldonado; Mateus Luís Barradas Paciencia; Liv Nunes Almeida Gomes; Marcelo Henrique Soller Ramada; Antonio Drauzio Varella (Phytochemistry Letters, 2025)

Enrichment planting to restore secondary forests in Central Amazon: A perspective on timber production and carbon sequestration - Guilherme Silva Modolo; Thalita Vitória Mamede Silva; Victor Alexandre Hardt Ferreira dos Santos; André Henrique Bueno Neves; Alaíde de Oliveira Carvalho; Gabriel Assis-Pereira; Mario Tomazello-Filho; Marciel José Ferreira (Forest Ecology and Management, 2025)

Envirotyping-informed mixed models to study the climatic drivers and yield seasonal variation for common beans in Brazil - Alexandre Bryan Heinemann; David Henriques da Matta; Luís Fernando Stone; Germano Costa-Neto; Rafael T. Resende; Paulo Augusto de O. Gonçalves; Ludmilla Ferreira Justino (European Journal of Agronomy, 2025)

The critically endangered Araripe Manakin (Antilophia bokermanni) is uninfected by, but probably susceptible to, haemosporidians in northeastern Brazil - Verônica L. Silva; João H. Oliveira; Pedro Henrique O. Pereira; Geovana S. Sandes; Érika M. Braga; Alexandre M. Fernandes (Journal of Ornithology, 2025)

Boosting carbon sequestration by using forage grass in tropical deep soil with no-tillage - João Henrique dos Santos Ferreira; José Roberto Portugal; Matheus Fróes; João William Bossolani; Juliano Carlos Calonego; Carlos Alexandre Costa Crusciol (Agriculture, Ecosystems & Environment, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Assessing stock status and abundance trends of King Mackerel (Scomberomorus cavalla) using a maturity-based approach: A comparison across local and regional scales - Luís Henrique França; Alexandre Ricardo dos Santos Jr.; Walter Dennis Menezes de Oliveira; Beatrice Padovani Ferreira; Jorge Eduardo Lins Oliveira; Marcelo Francisco Nóbrega (Regional Studies in Marine Science, 2025)

On the importance of digital soil mapping scale for ecosystem service assessment and policy - A study involving soil sediments dynamic and direct aquifer recharge - Fernanda Almeida Bócoli; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Michele Duarte de Menezes; Alexandre Uezu; Nilton Curi; Sérgio Henrique Godinho Silva (Geoderma Regional, 2025)

Biochar Application to Recover Degraded Soils: Comparison of Different Biomass Sources Assessed by Soil Physical Quality and Maize Growth - Tiago da Costa Dantas Moniz; João Marcos Rodrigues dos Santos; Gilvanete da Silva Henrique; Francisco Luan Almeida Barbosa; João Ivo Rodrigues de Sousa; Ícaro Vasconcelos do Nascimento; Alexandre dos Santos Queiroz; Carlos Tadeu dos Santos Dias; Maria Vitória Ricarte Gonçalves; Mirian Cristina Gomes Costa; Helon Hébano de Freitas Sousa; Francisca Gleiciane da Silva; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Engaging and legitimizing communities: co-designing a community-based Marine Protected Area - Mafalda Rangel; Barbara Horta e Costa; Mª Helena Guimarães; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos ML Afonso; et al. (Marine Policy, 2025)

A feasibility analysis of barocaloric refrigeration using PDMS as a solid-state refrigerant - Pedro Henrique Oliveira Faria; Alexandre Magnus Gomes Carvalho; Pablo Adamoglu de Oliveira; Paulo Vinicius Trevizoli (International Journal of Refrigeration, 2025)

Single-cell proteins as alternative sources of proteins and nutrients - Sílvio Jackson Félix Alves; Elizabeth Bárbara Epalanga Pires; Marcela Aparecida da Silva Alexandre; Claudia Cristina Auler do Amaral Santos; José Guilherme Prado Martin; Pedro Henrique Campelo; Evandro Martins; Monique Renon Eller (Food Research International, 2025)

Impact of carbon footprint of food production on consumer perceptions and attitudes: Insights from text highlighting - Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Alexandre Henrique Silas Souza; Fabiana Borges Ribeiro; Taynara de Oliveira Ferreira; Laura Falavinha Vieira Bresciani; Jéssica Ferreira Rodrigues (Food Quality and Preference, 2025)

Single-step genomic best linear unbiased predictions of sugarcane genotype performance - Mateus Teles Vital Gonçalves; Kaio Olimpio das Graças Dias; Guilherme da Silva Pereira; Pedro Henrique Silva Ferreira; Márcio Henrique Pereira Barbosa; Gota Morota; Luiz Alexandre Peternelli (Euphytica, 2025)

GM1 oligosaccharide-mediated rescue in GBA-linked Parkinson’s disease via modulation of lysosomal and mitochondrial dysfunctions - Giulia Lunghi; Carola Pedroli; Ilaria Tagliabue; Dorina Dobi; Maria Grazia Ciampa; Laura Mauri; Laura Rouvière; Alexandre Henriques; Noelle Callizot; Sandro Sonnino; Elena Chiricozzi; Maria Fazzari (Glycoconjugate Journal, 2025)

Assessing sediment and nutrient transport in a South Brazilian catchment: hysteresis, fingerprinting, and management implications - Alice Prates Bisso Dambroz; Jean Paolo Gomes Minella; Paul David Capel; Felipe Bernardi; Larissa Werle; João Henrique Stibe Silva; Alexandre Augusto Schlesner; Lidiane Buligon; Fábio Joel Kochem Mallmann; Claudia Alessandra Peixoto de Barros; Tales Tiecher; Olivier Evrard; et al. (Environmental Monitoring and Assessment, 2025)

Synergistic effect of dual pretreatments and temperature gradients on convective drying and preservation of bioactive compounds in purple sweet potato - Gabriel Monteiro da Silva; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Eugênia Telis de Vilela Silva; Henrique Valentim Moura; Aline Priscila de França Silva; Newton Carlos Santos; Yaroslávia Ferreira Paiva; Francislaine Suelia dos Santos; Inácia dos Santos Moreira; Ana Regina Nascimento Campos (Food and Bioproducts Processing, 2025)

Entropy-Based Measure of Rock Sample Heterogeneity Derived from Micro-CT Images - Luan Coelho Vieira da Silva; Júlio de Castro Vargas Fernandes; Felipe Bevilaqua Foldes Guimarães; Pedro Henrique Braga Lisboa; Carlos Eduardo Menezes dos Anjos; Thais Fernandes de Matos; Marcelo Ramalho Albuquerque; Rodrigo Surmas; Alexandre Gonçalves Evsukoff (Transport in Porous Media, 2025)

Interrelating neuronal morphology by coincidence similarity networks - Alexandre Benatti; Henrique Ferraz De Arruda; Luciano Da Fontoura Costa (Journal of Theoretical Biology, 2025)

Establishment of Psychotria viridis Ruiz & Pav. callus cultures, plantlet regeneration and in vitro production of the hallucinogenic indole alkaloid N,N-dimethyltryptamine - Camila Moreno Lopes de Andrade; Beatriz Aparecida Passos Paranhos Bismara; Fabiana Pereira Santos; Maurício Yonamine; José Alexandre de Souza Crippa; Jaime Eduardo Cecílio Hallak; Fernando Henrique Ferrari Alves; Moacir Pasqual; Vanessa Cristina Stein (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Effects of Phosphate Solubility on Soil P Pools, Nutrition, and Growth of Eucalyptus Over an Eight-Year Rotation - Adam da Cruz Rodrigues; Estela Covre Foltran; Ana Paula Bettoni Teles; Antonio Leite Florentino; Silvio Henrique Menezes Gomes; José Henrique Tertulino Rocha; Paulo Sergio Pavinato; José Henrique Bazani; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves (Journal of Soil Science and Plant Nutrition, 2025)

Exploring sexual dimorphism and growth patterns in Aegla aff. castro (Crustacea: Aeglidae): insights into reproductive and competitive strategies - Pedro Henrique Reis; Eduardo Antonio Bolla; Alexandre Ribeiro da Silva; AntonioLeão Castilho (Invertebrate Reproduction & Development, 2025)

Antifungal resistance in yeasts from One Health perspective: A Brazilian study - Rafael Wesley Bastos; Nalu Teixeira de Aguiar Peres; Kássia Jéssica Galdino da Silva; Ludmila Gouveia Eufrasio; Daniel Santana de Carvalho; Gabriela Silva Cruz; Fabíola Lucini; Lorena Souza Silva; Sthefany Emanuelle Silva; Hareton Teixeira Vechi; Manoella do Monte Alves; Luciana Rodrigues Ferreira Ribeiro; et al. (Science of The Total Environment, 2025)

Performance and feed intake of Nellore steers in extensive, intensive, and integrated pasture-based beef cattle production systems - Rolando Pasquini Neto; Althieres José Furtado; Gabriele Voltareli da Silva; Annelise Aila Gomes Lobo; Adibe Luiz Abdalla Filho; Flavio Perna Junior; Alexandre Berndt; Sérgio Raposo de Medeiros; André de Faria Pedroso; Patrícia Perondi Anchão de Oliveira; Paulo Henrique Mazza Rodrigues (Livestock Science, 2025)

Hydrogen-powered future: Catalyzing energy transition, industry decarbonization and sustainable economic development: A review - Bruno Augusto Cabral Roque; Matheus Henrique Castanha Cavalcanti; Pedro Pinto Ferreira Brasileiro; Paulo Henrique Ramalho Pereira Gama; Valdemir Alexandre dos Santos; Attilio Converti; Mohand Benachour; Leonie Asfora Sarubbo (Gondwana Research, 2025)

Designing Burn Windows for Integrated Fire Management in Wetlands: Why Should Flooding Not Be Overlooked? - Maxwell da Rosa Oliveira; Alexandre de Matos Martins Pereira; Francielli Bao; Bruno Henrique dos Santos Ferreira; Adriana Espinoza Fernando; Fabio de Oliveira Roque; Arnildo Pott; Geraldo Alves Damasceno-Junior; Danilo Rafael Mesquita Neves (Wetlands, 2025)

Spatio-temporal dynamics of water stress for common bean production in Goiás, Brazil - Ludmilla Ferreira Justino; Alexandre Bryan Heinemann; David Henriques da Matta; Luís Fernando Stone; Paulo Augusto de Oliveira Gonçalves; Silvando Carlos da Silva (Theoretical and Applied Climatology, 2025)

Silvopastoral system as a climate-smart alternative for beef production: Enteric methane emission neutralization and animal thermal comfort increase - Henrique B. Brunetti; Patrícia P.A. Oliveira; José R.M. Pezzopane; Alberto C. de C. Bernardi; Alexandre R. Garcia; Alexandre Berndt; André de F. Pedroso; Ana L.J. Lelis; Sérgio R. Medeiros (Agricultural Systems, 2025)

Potentiating-antibiotic and antibacterial properties of Luetzelburgia auriculata (ALLEMÃO) Ducke against MDR bacterial strains - Thiago S. Freitas; Janaina E. Rocha; Marcos J. F. Lima; Carla F. A. Nonato; Cicera J. Camilo; Cicera L. R. Paulo; Maria A. S. Alencar; Isaac M. Araújo; Karla S. T. G. Belém; Selvina P. Silva; Francisco N. Pereira Junior; Hélcio S. Santos; et al. (Vegetos, 2025)

Chemical annotation of the infusion of Jungia floribunda Less and its inhibitory potential on the elastase enzyme - Andreza Aparecida Ribeiro; Jorge Alexandre Nogueira Santos; Paula Pio de Oliveira Salem; Mario Ferreira Conceição Santos; Paula Carolina Pires Bueno; João Henrique Ghilardi Lago; Danielle Ferreira Dias; Daniela Aparecida Chagas de Paula; Marisi Gomes Soares (Natural Product Research, 2025)

Organic carbon stocks across various land use systems in Sandy Ultisols and Oxisols in Brazil - Maria Cecília Vieira Totti; Yuri Lopes Zinn; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Andrés Olaya Montes; Salvador Francisco Acuña-Guzman; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2025)

Chemical characterization, antibacterial and antifungal activity of honey pots and pollen pots obtained from the stingless bee Tetragonisca angustula (Latreille, 1811) - Nair Silva Macêdo; Zildene de Sousa Silveira; Débora Menezes Dantas; Cristina Rodrigues dos Santos Barbosa; Antonia Thassya Lucas dos Santos; Thiago Araújo de Medeiros Brito; Josean Fechine Tavares; Débora Odília Duarte Leite; Priscilla Ramos Freitas Alexandre; José Galberto Martins da Costa; Cícera Datiane de Morais Oliveira-Tintino; Henrique Douglas Melo Coutinho; et al. (Food and Chemical Toxicology, 2025)

Blanching, cooking, and ethanol are effective strategies for preserving biofunctional compounds in purple-fleshed sweet potato powder - Gabriel Monteiro da Silva; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Eugênia Telis de Vilela Silva; Henrique Valentim Moura; Aline Priscila de França Silva; Newton Carlos Santos; Flávia Carolina Alonso Buriti; Ana Júlia de Brito Araújo Carvalho; Marcos dos Santos Lima (Food and Bioproducts Processing, 2025)

Modulation of Eimeria spp. parasite load on productivity parameters in lambs fed with babassu byproduct - Sara Silva Reis; Henrique Nunes Parente; Anderson de Moura Zanine; Gisele Thamires Araújo da Silveira; Edegleicia Alves de Sousa; Arlan Araújo Rodrigues; Thalia Caldas da Silva; José Gracione do Nascimento Souza Filho; Janaina Marques do Nascimento; Thiago Vinicius Costa Nascimento; Michelle de Oliveira Maia Parente; Carlos Rodrigo Hermosilla; et al. (Tropical Animal Health and Production, 2025)

Rice Culture Systems in Soils with Aluminum: A Morphological and Developmental Analysis - Lucas Aparecido Manzani Lisboa; Gustavo Henrique de Oliveira Dias; Kauê Barbarotto Ribeiro; Edison Alves Rocha; Lauro Kenji Komuro; Paulo Alexandre Monteiro de Figueiredo (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Characterization of common bean production regions in Brazil using machine learning techniques - Ludmilla Ferreira Justino; Alexandre Bryan Heinemann; David Henriques da Matta; Luís Fernando Stone; Paulo Augusto de Oliveira Gonçalves; Silvando Carlos da Silva (Agricultural Systems, 2025)

Lippia origanoides essential oil increases longevity and ameliorates β-amyloid peptide-induced toxicity in Caenorhabditis elegans - Ana Maria Henrique Moniz; Francisco Humberto Xavier Junior; Giovanna Melo Martins Silva; Ana Cristina Gonçalves Reis de Melo; Maylla Maria Correia Leite Silva; Weslley Souza Paiva; Hugo Alexandre Oliveira Rocha; Luiz Antônio Mendonça Alves da Costa; Antônio Alves de Melo Filho; Riva de Paula Oliveira (Natural Product Research, 2025)

Multivariate statistical analysis of surface water quality in the capibaribe river (Pernambuco state, Northeast Brazil): Contributions to water management - Jaqueline dos Santos Silva; Livia Caroline Alexandre de Araújo; Milena Danda Vasconcelos; Iago José Santos da Silva; Fabricio Motteran; Rosner Henrique Alves Rodrigues; Carina Lucena Mendes-Marques; Rayanna Barroso de Oliveira Alves; Hernande Pereira da Silva; Maria Paloma Barros; Sivoneide Maria da Silva; Guilherme Malafaia; et al. (Marine Environmental Research, 2025)

Phylogenetic analyses reveal only Albugo rorippae causing white rust on horseradish in Brazil - Marlon Henrique Hahn; Erica Camila Zielinski; Alexandre Claus; Gabriel Koch; Jhulia Gelain; Danilo Batista Pinho; Henrique da Silva Silveira Duarte (Crop Protection, 2025)

Large pelagic fish exploitation by longliners in the Atlantic Ocean and Mediterranean Sea: A contribution to spatial planning and sustainable fisheries - Marcelo Francisco Nóbrega; Luis Henrique França; Alexandre Ricardo dos Santos Junior; Jorge Eduardo Lins Oliveira (Fisheries Research, 2025)

Exploring the orphan immune receptor TREM2 and its non-protein ligands: In silico characterization - Pedro Henrique dos Santos Dantas; Vinícius Alexandre Fiaia Costa; Andrei Giacchetto Felice; Eduarda Guimarães Sousa; Amanda de Oliveira Matos; Siomar de Castro Soares; Marcelle Silva-Sales; Bruno Junior-Neves; Helioswilton Sales-Campos (Chemistry and Physics of Lipids, 2025)

Retraction notice to “Using structural equation modeling to assess the genotoxic and mutagenic effects of heavy metal contamination in the freshwater ecosystems: A study involving Oreochromis niloticus in an urban river” [Sci. Total Environ. 913 (2024) 169529] - Jordany Gomes da Silva; Cristiano Aparecido Chagas; Talita Giselly dos Santos Souza; Marlyete Chagas de Araújo; Lívia Caroline Alexandre de Araújo; André Maurício Melo Santos; Rafael Artur de Queiroz Cavalcanti de Sá; Rayanna Barroso de Oliveira Alves; Rosner Henrique Alves Rodrigues; Hernande Pereira da Silva; Guilherme Malafaia; Ranilson de Souza Bezerra; et al. (Science of The Total Environment, 2024)

A transcontinental threat: Plastic waste from Africa invades Brazil's coast - Lucio Brabo; Laercio L. Martins; Ryan Andrades; Carlos E.P. Teixeira; Adriana Pereira do Nascimento; Rufino Neto Andrade de Azevedo; Luís E.A. Bezerra; Rivelino M. Cavalcante; Kelly Ferreira Cottens; Romulo Alexandre Soares; Paulo Henrique Gomes de Oliveira Sousa; Tarin F. Mont'Alverne; et al. (Science of The Total Environment, 2024)

Arsenic, cadmium, and chromium concentrations in contrasting phosphate fertilizers and their bioaccumulation by crops: Towards a green label? - Mariana Rocha de Carvalho; Thiago Adorno de Almeida; Gustavo Avelar Zorgdrager Van Opbergen; Fábio Henrique Alves Bispo; Lívia Botelho; Alexandre Boari de Lima; Paulo Eduardo Ribeiro Marchiori; Luiz Roberto Guimarães Guilherme (Environmental Research, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Supplementation with 25-hydroxicolecalciferol increases the nutritional efficiency and carcass growth of grazing Nellore young bulls - Fernanda S. Mudado; Melissa B. Silveira; Henrique J. Fernandes; Alexandre Perdigão; Diego M.M. dos Santos; Thomas H.R. da Silva; Jarbas M. da Silva Júnior; Isabelle E. de Matos; Victor V. de Carvalho; Tiago S. Acedo; Aline G. da Silva (Animal Feed Science and Technology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

First geological survey and characterisation of a giant depression in carbonate strata at the Rio Grande Rise (southwestern Atlantic) - Alexandre Henrique Ferraz; Christian Millo; Paulo César Fonseca Giannini; Thales Chamarelli Felipe; André Luiz Silva Pestilho; Lena Virgínia Soares Monteiro; Carina Ulsen; Bramley J. Murton; Luigi Jovane (Geomorphology, 2024)

The impact of plant-based product denomination on consumer expectations and sensory perception: A study with vegan chocolate dessert - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Júlia Fernanda Urbano Marinho; Juliana Santos Marques; Karen Lendengue de Matos Regalado; Ana Carla Marques Pinheiro (Food Research International, 2024)

Phonolite rock powder promotes adequate K and Na nutrition and cycling in eucalypt stands even during drought - Fábio Henrique Silva Floriano de Toledo; Yesid Alejandro Mariño Macana; Alexandre de Vicente Ferraz; Eric Victor de Oliveira Ferreira; Patrícia Andressa de Ávila; Liamara Santos Masullo; Gabriela Gonçalves Moreira; Rodrigo E. Hakamada; Cindy E. Prescott; José Leonardo de Moraes Gonçalves (New Forests, 2024)

Long-term trends in the functional structure of estuarine fish assemblages in a subtropical estuary and its relationships with local environmental variability, man-made changes, and climatic drivers - Erika Belarmino; Henrique Cabral; Alexandre Miranda Garcia (Marine Environmental Research, 2024)

Temporal dominance of Sensations: Do different concepts of “dominance” affect the results? - Katiúcia Alves Amorim; Louise Paiva Passos; Alexandre Henrique Silas Souza; Vinícius dos Santos Cardoso; Rita de Cássia Vieira; Milene de Souza Campos; Jéssica Ferreira Rodrigues; Cleiton Antônio Nunes; Ana Carla Marques Pinheiro (Food Research International, 2024)

Flooding and fire frequency promotes beta diversity in tree and non-tree species in tropical wetlands - Bruno Henrique dos Santos Ferreira; Maxwell da Rosa Oliveira; Bruno Arguelho Arrua; Vivian Ayumi Fujizawa Nacagava; Rafaela Aparecida Mariano Fernandes; Alexandre de Matos Martins Pereira; Andréia de Carvalho Santos; Ademilson Costa; Mesaque Rocha; Silvio Xavier; Rubens Aquino Ferraz; Arnildo Pott; et al. (Forest Ecology and Management, 2024)

Improving preservation of bioactive compounds in mangosteen peel flour through pre-treatment with bleaching, ethanol, and vacuum pulse - Eugênia Telis de Vilela Silva; Alexandre José Melo de Queiroz; Rossana Maria Feitosa de Figueirêdo; Henrique Valentim Moura; Aline Priscila de França Silva; Gabriel Monteiro da Silva; Inácia dos Santos Moreira; Marcos dos Santos Lima; Ana Julia de Brito Araújo; Francislaine Suelia dos Santos (Food Bioscience, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd in a region without a cyclic vector - Luiz Fellipe Monteiro Couto; Thiago Souza Azeredo Bastos; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ricardo Backstron Falavigna; José Felipe Warmling Spricigo; Rinaldo Aparecido Mota; Breno Cayero Cruz; Marcos Henrique Alcantara Colli; Alexandre Braga Scarpa; Vando Edesio Soares; et al. (Veterinary Parasitology, 2024)

Association of emojis to the five basic tastes (sweet, salty, sour, bitter and umami) - Lenízy Cristina Reis Rocha; Louise Paiva Passos; Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Jéssica Ferreira Rodrigues; Ana Carla Marques Pinheiro (Food Quality and Preference, 2024)

Antimicrobial and antioxidant competence of sustainable grumixama leaves extracts in nanoemulsion system - Natália Silva de Farias; Rodrigo Henrique Saatkamp; Alexandre Luis Parize; Silvani Verruck; Carmen Maria Olivera Müller (Food and Bioproducts Processing, 2024)

Perovskite-type strontium ferrite-based catalyst: Characterization and antibiotic degradation approach - Afonso Henrique da Silva Júnior; Carlos Rafael Silva de Oliveira; Leandro Pellenz; Paulo Alexandre Durant Moraes; Willbrynner Pereira Marques; Luciana Prazeres Mazur; Thiago Guimarães Costa; Adolfo Horn Jr; Selene Maria de Arruda Guelli Ulson de Souza; Antônio Augusto Ulson de Souza; Luciano da Silva; Adriano da Silva (Process Safety and Environmental Protection, 2024)

Harnessing crop models and machine learning for a spatial-temporal characterization of irrigated rice breeding environments in Brazil - Alexandre Bryan Heinemann; Germano Costa-Neto; David Henriques da Matta; Igor Kuivjogi Fernandes; Luís Fernando Stone (Field Crops Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Texture prediction of natural soils in the Brazilian Amazon through proximal sensors - Quésia Sá Pavão; Paula Godinho Ribeiro; Gutierre Pereira Maciel; Sérgio Henrique Godinho Silva; Suzana Romeiro Araújo; Antonio Rodrigues Fernandes; José Alexandre Melo Demattê; Pedro Walfir Martins e Souza Filho; Silvio Junio Ramos (Geoderma Regional, 2024)

Edible hydrosoluble sachets produced with food by-products and natural additives - Alexandre M.S. Jorge; Cristiana S.A. Bento; Marta H.F. Henriques; Marisa C. Gaspar; Mara E.M. Braga (Food Hydrocolloids, 2024)

Hidden ecotoxicological dangers: Investigating pathogen circulation and non-toxic risks hazards in a crucial brazilian watershed - Milena Roberta Freire da Silva; Karolayne Silva Souza; Francisco Henrique Santana da Silva; Milena Danda Vasconcelos Santos; Bruno Oliveira de Veras; Iago José Santos da Silva; Fabricio Motteran; Ana Carolina de Oliveira Luz; Tereza Cristina Leal Balbino; Lívia Caroline Alexandre de Araújo; Guilherme Malafaia; Maria Betânia Melo de Oliveira (Aquatic Toxicology, 2024)

Occurrence of Alternaria alternata causing leaf spot on tamarillo in Brazil - Elizeu Junior da Silva; Alexandre Claus; Marlon Henrique Hahn; Gabriel Koch; Mayara Catherine Candido Silva; Renata Faier Calegario; Henrique da Silva Silveira Duarte (Crop Protection, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Hydro-morphological features and functional structure of fish assemblages mediate species isotopic niches in estuaries - Nils Teichert; Anne Lizé; Mario Lepage; Henrique Cabral; Thomas Trancart; Anthony Acou; Marie Larregieu; Eric Feunteun; Alexandre Carpentier (Estuarine, Coastal and Shelf Science, 2024)

New Perspectives in Stem Cell Transplantation and Associated Therapies to Treat Retinal Diseases: From Gene Editing to 3D Bioprinting - Gabrieli Bovi dos Santos; Théo Henrique de Lima-Vasconcellos; Marília Inês Móvio; Alexander Birbrair; Carolina Beltrame Del Debbio; Alexandre Hiroaki Kihara (Stem Cell Reviews and Reports, 2024)

Intraarticular monomethyl fumarate as a perspective therapy for osteoarthritis by macrophage polarization - Douglas Menezes de Souza; Kauê Franco Malange; Catarine Massucato Nishijima; Bruno Henrique de Melo Lima; Vinicius Cooper Capetini; Alexandre L. R. de Oliveira; Gabriel Forato Anhê; Claudia Herrera Tambeli; Carlos Amilcar Parada (Inflammopharmacology, 2024)

Mathematical models for predicting protodioscin in tropical forage grasses - Juliana Caroline Santos Santana; Gelson dos Santos Difante; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Henrique Jorge Fernandes; Camila Celeste Brandão Ferreira Ítavo; Vanessa Zirondi Longhini; Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo (Toxicon, 2024)

Quaternary sedimentation over the Precambrian basement of Borborema Province (NE, Brazil): Tectonic and climatic controls - Rizelda Regadas de Carvalho; Viviane Khoury Asfora; Willian Alexandre Lima de Moura; José Antonio Barbosa; Germano Mário Silva Ramos; Virgínio Henrique de Miranda Lopes Neumann (Journal of South American Earth Sciences, 2024)

Strategies for fungicide application based on the yield response of common bean genotypes under El Niño-Southern Oscillation (ENSO) - Alexandre Bryan Heinemann; Patrícia Valle Pinheiro; David Henriques da Matta; Luís Fernando Stone; Pedro Araújo Pietrafesa; William Rafael Ribeiro; Rodrigo Yoiti Tsukahara; Hélio Antônio Wood Joris (European Journal of Agronomy, 2024)

Nutritional strategies, performance, digestibility, and carcass traits of Santa Ines and Rabo Largo breeds in a tropical climate - Anderson Lopes Pereira; Michelle de Oliveira Maia Parente; Edegleicia Alves de Sousa; Arnaud Azevedo Alves; Anderson de Moura Zanine; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Francisca Cláudia da Silva de Sousa; Luana França dos Anjos; Hyanne Costa Lima; Miguel Arcanjo Moreira Filho; Hactus Souto Cavalcanti; et al. (Tropical Animal Health and Production, 2024)

Efficacy of calcium hypochlorite in disinfection of gutta-percha cones contaminated with Candida albicans - Guilherme Pauletto; Pedro Henrique Fortes Guerim; Arthur Brites Barbosa; Leonardo Quintana Soares Lopes; Carlos Alexandre Souza Bier; Patrícia Kolling Marquezan (Brazilian Journal of Microbiology, 2024)

RETRACTED: Using structural equation modeling to assess the genotoxic and mutagenic effects of heavy metal contamination in the freshwater ecosystems: A study involving Oreochromis niloticus in an urban river - Jordany Gomes da Silva; Cristiano Aparecido Chagas; Talita Giselly dos Santos Souza; Marlyete Chagas de Araújo; Lívia Caroline Alexandre de Araújo; Andr'e Maurício Melo Santos; Rafael Artur de Queiroz Cavalcanti de Sá; Rayanna Barroso de Oliveira Alves; Rosner Henrique Alves Rodrigues; Hernande Pereira da Silva; Guilherme Malafaia; Ranilson de Souza Bezerra; et al. (Science of The Total Environment, 2024)

Paleosol marked by contrasting formation processes: A pilot study using digital morphometrics in Southeastern Brazil - Fernanda Almeida Bócoli; Sérgio Henrique Godinho Silva; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Alexandre Uezu; Marco Aurélio Carbone Carneiro; Marta Vasconcelos Ottoni; et al. (CATENA, 2024)

Effects of diets differing in the concentrate-to-roughage ratio on meat quality and fatty acids composition in abomasal digesta and meat from thin-tail and fat-tail Brazilian ovine breeds - Luana França dos Anjos; Rui José Branquinho de Bessa; Henrique Nunes Parente; Susana Paula Alves; Aline Vieira Landim; Anderson de Moura Zanine; Anderson Lopes Pereira; Graziele Silva de Oliveira; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Mayara Raposo dos Santos; Michelle de Oliveira Maia Parente (Small Ruminant Research, 2023)

Remote sensing of the Earth's soil color in space and time - Rodnei Rizzo; Alexandre M.J.-C. Wadoux; José A.M. Demattê; Budiman Minasny; Vidal Barrón; Eyal Ben-Dor; Nicolas Francos; Igor Savin; Raul Poppiel; Nelida E.Q. Silvero; Fabrício da Silva Terra; Nícolas Augusto Rosin; et al. (Remote Sensing of Environment, 2023)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Constructing high-resolution stratigraphic frameworks by the application of signal analysis techniques: Example of Balbuena IV sequence, Yacoraite formation, Salta Basin - José Arthur Oliveira Santos; Alexandre Uhlein; Márcio Dantas; Gabriel de Morais Coutinho; Thomás Jung Spier; Kaio Henrique Masse Vieira; Alan Cabral Trindade Prado; Douglas Macharet; Gabriel Jubé Uhlein; Tiago Novo; Humberto Reis; Felipe Alves Farias; et al. (Marine and Petroleum Geology, 2023)

Doses of orange (Citrus sinensis) essential oil for Nellore steers fed with a forage-based diet - Letícia Carolina Bortolanza Soares; Alexandre Vaz Pires; Paulo César Gonzales Dias Junior; Isabela Jorge dos Santos; Rhaíssa Garcia de Assis; Flávio Perna Junior; Paulo Henrique Mazza Rodrigues; Janaina Socolovski Biava; Evandro Maia Ferreira; Daniel Montanher Polizel (Livestock Science, 2023)

Green roofs are effective in cooling and mitigating urban heat islands to improve human thermal comfort - Taize Calvacante Santana; Cristiane Guiselini; Abelardo Antônio de Assunção Montenegro; Héliton Pandorfi; Rodes Angelo Batista da Silva; Renan da Silva e Silva; Pedro Henrique Dias Batista; Sávio Duarte Lopes Cavalcanti; Nicoly Farias Gomes; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim (Modeling Earth Systems and Environment, 2023)

Doses of lemongrass (Cymbopogon citratus) essential oil for Nellore steers fed with a forage-based diet - Letícia Carolina Bortolanza Soares; Alexandre Vaz Pires; Paulo César Gonzales Dias Junior; Isabela Jorge dos Santos; Rhaíssa Garcia de Assis; Flavio Perna Junior; Evandro Maia Ferreira; Janaina Socolovski Biava; Paulo Henrique Mazza Rodrigues; Daniel Montanher Polizel (Livestock Science, 2023)

Campomanesia guazumifolia infusion decreases human platelet aggregation by reducing cyclooxygenase 1 activity and its underlying mechanisms - Caroline Honaiser Lescano; Fernando Freitas de Lima; Taline Baganha Stefanello Catelan; Victor Hugo Dantas Guimarães; Ulisses Alves Pereira; Charles Martins Aguilar; Cláudia Andrea Lima Cardoso; Sérgio Henrique Sousa Santos; Alexandre Borges; Ivan Pires de Oliveira (Food Bioscience, 2023)

Rickettsia communities and their relationship with tick species within and around the national park of Iguaçu, Brazil - Amália Regina Mar Barbieri; Adriane Suzin; Lais Miguel Rezende; Matheus Henrique Tognolli; Alexandre Vogliotti; Pablo Henrique Nunes; Graziela Tolesano Pascoli; Vanessa do Nascimento Ramos; Jonny Yokosawa; Maria Carolina de Azevedo Serpa; Samuel Fernando Adami; Marcelo B. Labruna; et al. (Experimental and Applied Acarology, 2023)

Temperature stratification in the Guanabara Bay and its relationship with wind-induced coastal upwelling off Cabo Frio, Brazil - Alexandre Macedo Fernandes; Elisa Nóbrega Passos; Paulo Henrique Rezende Calil; Gleyci Aparecida Oliveira Moser; Eduardo Negri de Oliveira; Rogério Pinto Espíndola (Estuarine, Coastal and Shelf Science, 2023)

Soil fertility, root growth, and Eucalypt productivity in response to lime and gypsum applications under soil water deficit - Yesid Alejandro Mariño Macana; Robson Schaff Corrêa; Fábio Henrique Silva Floriano de Toledo; Alexandre de Vicente Ferraz; Eric Victor de Oliveira Ferreira; Rodrigo Eiji Hakamada; Gabriela Gonçalves Moreira; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves (New Forests, 2023)

Edible films produced from agrifood by-products and wastes - Alexandre M.S. Jorge; Marisa C. Gaspar; Marta H.F. Henriques; Mara E.M. Braga (Innovative Food Science & Emerging Technologies, 2023)

Performing AI 55 or 65 h after progesterone device removal did not differ in a 7-d progesterone-based protocol for timed-AI in Nellore suckled cows - Marcos Vinicius de Castro Ferraz Junior; Ancelmo Rodrigues Cunha; Terezinha Teixeira de Souza; Bismarck Soares Alexandrino; Pedro Henrique Vilela de Carvalho; Alexandre Vaz Pires (Tropical Animal Health and Production, 2023)

Analysis of Goiás State rainfall and temperature similarity patterns during the El Niño-Southern Oscillation phenomenon phases across the years - David Henriques da Matta; Caio Augusto dos Santos Coelho; Leydson Lara dos Santos; Luís Fernando Stone; Alexandre Bryan Heinemann (Theoretical and Applied Climatology, 2023)

Genetic parameters and multi-trait genomic prediction for hemoparasites infection levels in cattle - Andrea Renata da Silva Romero; André Vieira do Nascimento; Marcia Cristina de Sena Oliveira; Cintia Hiromi Okino; Camila Urbano Braz; Daiane Cristina Becker Scalez; Diercles Francisco Cardoso; Fernando Flores Cardoso; Claudia Cristina Gulias Gomes; Alexandre Rodrigues Caetano; Humberto Tonhati; Cedric Gondro; et al. (Livestock Science, 2023)

Conditioned medium of mesenchymal stem cells: application in mares with endometrial fibrosis - Fabiano Trevisan da Rocha; Janislene Mach Trentin; Henrique Boll de Araújo Bastos; Rômulo Oliveira Fernandes da Silva; Matheus Souto de Freitas; Rodrigo Costa Mattos; Nélson Alexandre Kreztmann Filho; Mara Iolanda Batistella Rubin (Journal of Equine Veterinary Science, 2023)

Treatments for the control of Neoechinorhynchus buttnerae (Acanthocephala) in tambaqui Colossoma macropomum - Bruna Rafaela Caetano Nunes; Yuri Vinicius de Andrade Lopes; Ricardo Henrique B. de Souza; Raul Dirceu Pazdiora; Thiago Tetsuo Ushizima; Simone Paiva Medeiros; Lorrayne Tavares Corrêa; Igor Izidoro Cardoso; Matheus Vitor Vieira Andrade; Patricia Oliveira Maciel-Honda; Edsandra Campos Chagas; Fernanda de Alexandre Sebastião (Aquaculture International, 2023)

High-resolution sequence stratigraphy applied to reservoir characterization of the Brazilian Cretaceous pre-salt section, Campos Basin: Guidelines for geological modeling and reservoir management - Daniel Galvão Carnier Fragoso; Anderson Henrique de Melo; Lucas Arienti Gonçalves; Rodrigo Brandão Bunevich; Julio de Aratanha Maia Araujo; Thiago Camanho da Costa; Carlos Alexandre Pedrosa; Claiton Marlon Dos Santos Scherer (Marine and Petroleum Geology, 2023)

Fibrous microplastics released from textiles: Occurrence, fate, and remediation strategies - Carlos Rafael Silva de Oliveira; Afonso Henrique da Silva Júnior; Jéssica Mulinari; Alexandre José Sousa Ferreira; Adriano da Silva (Journal of Contaminant Hydrology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Methods of adventitious rooting of rootstocks for quince trees - Carlos Henrique Milagres; Lucídio Henriques Vote Fazenda; Alexandre Dias da Silva; Pedro Maranha Peche; Laise de Jesus dos Santos; Rafael Pio; Fábio Akira Mori (Rhizosphere, 2023)

Tracing the origin of deposited sediments: A study applying proximal sensing in a drainage subbasin - Wellington de Lima; Marcelo Mancini; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Salvador Francisco Acuña-Guzman; José Alexandre Melo Demattê; Nilton Curi (Journal of South American Earth Sciences, 2023)

Spread of Striga asiatica through suitable climatic conditions: Risk assessment in new areas producing Zea mays in South America - Fausto Henrique Vieira Araújo; José Carlos Barbosa dos Santos; Jose Barbosa dos Santos; Alexandre Ferreira da Silva; Rodrigo Soares Ramos; Ricardo Siqueira da Silva; Farzin Shabani (Journal of Arid Environments, 2023)

Seasonality does not influence cortisol or testosterone production, or seminal quality of stallions located at low latitudes - Mariane Leão Freitas; João Henrique Moreira Viana; Margot Alves Nunes Dode; Selma Regina Maggiotto; Ivo Pivato; Thiago Rodrigues Cardoso Braga; Alexandre In Piao Gomes Lim; Rodrigo Arruda de Oliveira (Animal Reproduction Science, 2023)

Effects of injectable and intravaginal progesterone on ewes’ reproductive performance at breeding season beginning - Taylon Antonio Sales da Silva; Evandro Maia Ferreira; Terezinha Teixeira de Souza; José Paulo Roman Barroso; Janaina Socolovski Biava; Alexandre Vaz Pires; Pedro Henrique Vilela Carvalho; Marcos Vinicius de Castro Ferraz Junior (Tropical Animal Health and Production, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

Selenium Content in Freshwater and Marine Fish from Southern Brazil Coastal Plain: a Comparative Analysis on Environmental and Dietary Aspects - Alexandre Henrique Ferraz; Larissa Pinheiro Costa; Nicolai Mirlean; Elisa Rosa Seus-Arrache; Segun Adebayo (Biological Trace Element Research, 2023)

Decoupling carry-over effects from environment in fish nursery grounds - Nils Teichert; Anne Lizé; Henrique Cabral; Anthony Acou; Thomas Trancart; Laure-Sarah Virag; Eric Feunteun; Alexandre Carpentier (Science of The Total Environment, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Mangrove microbial community recovery and their role in early stages of forest recolonization within shrimp ponds - Miguel Loiola; Amaro Emiliano Trindade Silva; Marcos Krull; Felipe Alexandre Barbosa; Eduardo Henrique Galvão; Vinicius F. Patire; Igor Cristino Silva Cruz; Francisco Barros; Vanessa Hatje; Pedro Milet Meirelles (Science of The Total Environment, 2023)

Environmental degradation of vegetation cover and water bodies in the semiarid region of the Brazilian Northeast via cloud geoprocessing techniques applied to orbital data - Jhon Lennon Bezerra da Silva; Geber Barbosa de Albuquerque Moura; Marcos Vinícius da Silva; José Francisco de Oliveira-Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Daiana Caroline Refati; Ricardo da Cunha Correia Lima; Ailton Alves de Carvalho; Maria Beatriz Ferreira; José Ivaldo Barbosa de Brito; Roni Valter de Souza Guedes; Pabrício Marcos Oliveira Lopes; et al. (Journal of South American Earth Sciences, 2023)

High spatial resolution data obtained by GNSS and RPAS to assess islets flood-prone scenarios for 2100 - Rodrigo Mikosz Gonçalves; Júlia Isabel Pontes; Flávia Helena Manhães Vasconcellos; Lígia Albuquerque de Alcântara Ferreira; Heithor Alexandre de Araújo Queiroz; Paulo Henrique Gomes de Oliveira Sousa (Applied Geography, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Antimicrobial activity of dimeric acylphloroglucinols isolated from southern Brazilian Hypericum species against to resistant bacterial - Henrique Bridi; Ana Paula Pustay; Sérgio Augusto de Loreto Bordignon; Simone Ulrich Picoli; Gilsane Lino von Poser; Alexandre de Barros Falcão Ferraz (Natural Product Research, 2022)

The addition of different oils in the diet regulates the expression of adipocytokine signaling genes in sheep longissimus dorsi muscle - Paulo Henrique Souza; Edwana Mara Moreira Monteiro; Elizabeth Machado Barbosa; Alexandre Rosário Casseb; Wilson Amaro Conde Moreira Sobrinho; Felipe Nogueira Domingues; Cristian Faturi; Aníbal Coutinho Rêgo; Ednaldo Silva Filho (Tropical Animal Health and Production, 2022)

Co-design of a marine protected area zoning and the lessons learned from it - Barbara Horta e Costa; M. Helena Guimarães; Mafalda Rangel; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos M. L. Afonso; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) are a tool to safeguard marine natural systems, yet their effectiveness depends on how well they are integrated into the existing socioeconomic context. Stakeholder engagement in MPA design can contribute to increasing integration. This study focuses on the co-design of an MPA between researchers, public administration, the private sector, and non-governmental organizations. The proposed MPA is in Portugal and includes an area that is a hotspot for biodiversity and economic activities. This is the first MPA proposal in mainland Portugal co-designed using a participatory approach. This study highlights the steps of the zoning process and synthesizes the eight main lessons learned, useful for other cases, particularly for relatively small coastal MPAs with multiple socioeconomic activities. Three zoning proposals were developed and discussed within the participatory process. The proposals considered the best scientific and local knowledge available and were defined using ecological, socioeconomic, and shape-area guiding principles. In an iterative manner and following a participatory approach, compromises with stakeholders were achieved, and a final proposal, scientifically sound and socially accepted by most stakeholders, was delivered to the government. The final zoning plan will achieve ambitious conservation goals, including the largest fully protected area to be declared in mainland Portugal, while minimizing the impacts on the existing economic activities and promoting its sustainability. This process resulted in valuable lessons that may be applied elsewhere and guide future MPA implementation or rezoning of existing ones. These transdisciplinary and participatory processes can be time and resource-consuming but are vital for ensuring MPA effectiveness.

An Evaluation of the Potential Use of Microbial Fuel Cells for Energy Production and Simultaneous Acid Mine Drainage Treatment - Luiz Henrique Zim Alexandre; Tatiana Gisset Pineda-Vásquez; Elise Sommer Watzko; Derce de Oliveira Souza Recouvreux; Regina Vasconcellos Antônio (Water, Air, & Soil Pollution, 2022)

Long‐term unsustainable patterns of development rather than recent deforestation caused the emergence of Orthocoronavirinae species - Sérvio P. Ribeiro; Debmalya Barh; Bruno Silva Andrade; Raner José Santana Silva; Diogo Henrique Costa‐Rezende; Paula Luize Camargos Fonseca; Sandeep Tiwari; Marta Giovanetti; Luiz Carlos Junior Alcantara; Vasco Ariston Azevedo; Preetam Ghosh; José Alexandre F. Diniz‐Filho; et al. (Environmental Microbiology, 2022)
We investigated whether a set of phylogeographical tracked emergent events of Orthocoronavirinae were related to developed, urban and polluted environments worldwide. We explored coronavirus records in response to climate (rainfall parameters), population density, CO 2 emission, Human Developmental Index (HDI) and deforestation. We contrasted environmental characteristics from regions with spillovers or encounters of wild Orthocoronavirinae against adjacent areas having best‐preserved conditions. We used all complete sequenced CoVs genomes deposited in NCBI and GISAID databases until January 2021. Except for Deltacoronavirus, concentrated in Hong Kong and in birds, the other three genera were scattered all over the planet, beyond the original distribution of the subfamily, and found in humans, mammals, fishes and birds, wild or domestic. Spillovers and presence in wild animals were only reported in developed/densely populated places. We found significantly more occurrences reported in places with higher HDI, CO 2 emission, or population density, along with more rainfall and more accentuated seasonality. Orthocoronavirinae occurred in areas with significantly higher human populations, CO 2 emissions and deforestation rates than in adjacent locations. Intermediately disturbed ecosystems seemed more vulnerable for Orthocoronavirinae emergence than forested regions in frontiers of deforestation. Sadly, people experiencing poverty in an intensely consumerist society are the most vulnerable.

Short-term effects of phosphorus fertilization on Amazonian tree species in a mixed plantation - Alaíde de Oliveira Carvalho; André Henrique Bueno Neves; Matheus Luvison; Zilza Thayane Matos Guimarães; Victor Alexandre Hardt Ferreira dos Santos; Marciel José Ferreira (New Forests, 2022)

Genetic gains in Passiflora for resistance to cowpea aphid-borne mosaic virus using recurrent selection - Débora Souza Mendes; Alexandre Pio Viana; Eileen Azevedo Santos; Natan Ramos Cavalcante; Cleidiane Alves Rodrigues; Joameson Antunes Lima; Ravena Ferreira Vidal; Fernando Henrique de Barros Walter; Luan Baritiello da Silva Bezerra; Marcelo Eiras; Huarrisson Azevedo Santos (Euphytica, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Integrated analysis reveals a new species of Corydoras Lacépède, 1803 (Siluriformes: Callichthyidae) in the lower Iguassu River, Brazil - Rafael Henrique da Rocha; Carlos Alexandre Fernandes; Thaís Souto Bignotto; Vladimir Pavan Margarido; Luiz Fernando Caserta Tencatt; Weferson Júnio da Graça; Éder André Gubiani (Organisms Diversity & Evolution, 2022)

Evaluation of the antifungal activity of α, β, and δ-damascone and inclusion complexes in β-cyclodextrin against Candida spp - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Antonia Thassya Lucas dos Santos; Francisco Lucas Alves Batista; Roger Henrique Sousa da Costa; Anita Oliveira Brito Pereira Bezerr Martins; Beatriz Gonçalves da Cruz; Maria Flaviana Bezerra Morais-Braga; Henrique Douglas Melo Coutinho; Francisco Ernani Alves Magalhães; Diniz Maciel de Sena Junior; Alexandre Magno Rodrigues Teixeira; et al. (Folia Microbiologica, 2022)

Adaptability and stability of soybean (Glycine max L.) genotypes in semiarid conditions - José Ricardo Tavares de Albuquerque; Hamurábi Anizio Lins; Manoel Galdino dos Santos; Márcio Alexandre Moreira de Freitas; Fernando Sarmento de Oliveira; Almir Rogério Evangelista de Souza; Lindomar Maria da Silveira; Glauber Henrique de Sousa Nunes; Aurélio Paes Barros Júnior; Paulo Fernando de Melo Jorge Vieira (Euphytica, 2022)

Ventrolateral periaqueductal gray matter integrative system of defense and antinociception - Gustavo Henrique de Mello Rosa; Farhad Ullah; Yara Bezerra de Paiva; Juliana Almeida da Silva; Luiz Guilherme S. Branco; Alexandre Pinto Corrado; Priscila Medeiros; Norberto Cysne Coimbra; Audrey Franceschi Biagioni (Pflügers Archiv - European Journal of Physiology, 2022)
Defensive responses are neurophysiological processes crucial for survival during threatening situations. Defensive immobility is a common adaptive response, in rodents, elaborated by ventrolateral periaqueductal gray matter (vlPAG) when threat is unavoidable. It is associated with somatosensory and autonomic reactions such as alteration in the sensation of pain and rate of respiration. In this study, defensive immobility was assessed by chemical stimulation of vlPAG with different doses of NMDA (0.1, 0.3, and 0.6 nmol). After elicitation of defensive immobility, antinociceptive and respiratory response tests were also performed. Results revealed that defensive immobility was followed by a decrease in the nociceptive perception. Furthermore, the lowest dose of NMDA induced antinociceptive response without eliciting defensive immobility. During defensive immobility, respiratory responses were also disturbed. Interestingly, respiratory rate was increased and interspersed with prolonged expiratory phase of breathing. These findings suggest that vlPAG integrates three different defensive behavioral responses, contributing to the most effective defensive strategies during threatening situations.

Characterisation of Trichoderma strains using FTIR-ATR spectroscopy and molecular analysis - Lucas Henrique Fantin; Ana Lúcia de Souza Madureira Felício; Ciro Hideki Sumida; Ricardo Marcelo Gonçalves; Karla Braga; José Alexandre de França; Marcelo Giovanetti Canteri (European Journal of Plant Pathology, 2022)

Modulation of structural carbohydrates, phenol compounds and lignin content in Eucalyptus urophylla cuttings grown under boron, copper and zinc induced-deficiency - Liamara Santos Masullo; Vitória Duarte Derisso; Gislene Roberta Manarim; Alexandre de Vicente Ferraz; José Henrique Tertulino Rocha; Patrícia Andressa de Ávila; Antonio Leite Florentino; Claudio Lima de Aguiar; José Lavres; José Leonardo de Moraes Gonçalves (New Forests, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Benthic Cyanobacterial Diversity and Antagonistic Interactions in Abrolhos Bank: Allelopathy, Susceptibility to Herbivory, and Toxicity - Felipe de Vargas Ribeiro; Taiara Aguiar Caires; Marcela Alvarenga de Almeida Simões; Paulo Iiboshi Hargreaves; Livia Bonetti Villela; Giovana de Oliveira Fistarol; Alexandre Brauns Cazelgrandi; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Renato Crespo Pereira; Paulo Sergio Salomon (Frontiers in Marine Science, 2022)
Benthic cyanobacterial mats (BCMs) are conspicuous components of coral reef communities, where they play key ecological roles as primary producers among others. BCMs often bloom and might outcompete neighboring benthic organisms, including reef-building corals. We investigated the cyanobacterial species composition of three BCMs morphotypes from the marginal reef complex of Abrolhos Bank (Southeastern Brazil). Also, we assessed their allelopathic effects on coral zooxanthellae, their susceptibility to herbivory by fish, and their toxicity to brine shrimp nauplii. Morphology and 16S rDNA sequencing unveiled the cyanobacteria Moorena bouillonii , Okeania erythroflocculosa , Adonisia turfae , Leptolyngbya sp., and Halomicronema sp. as components of BCMs from Abrolhos. BCMs cell-free filtrates and extracts exerted an allelopathic effect by reducing the growth of the ex hospite Symbiodinium sp. in culture. BCMs-only treatments remained untouched in field susceptibility assays in contrast to macroalgae only and mixed BCMs-macroalgae treatments that had the macroalgae fully removed by reef fish. Crude aqueous extracts from BCMs were toxic to brine shrimps in acute assays. Besides unveiling the diversity of BCMs consortia in Abrolhos, our results cast some light on their allelopathy, antiherbivory, and toxicity properties. These antagonistic interactions might promote adverse cascading effects during benthic cyanobacteria blooms and in gradual shifts to BCMs-dominated states.

Elusive deer occurrences at the Atlantic Forest: 20 years of surveys - Márcio Leite de Oliveira; Francisco Grotta-Netto; Pedro Henrique de Faria Peres; Alexandre Vogliotti; Carlos Rodrigo Brocardo; Jorge José Cherem; Mariana Landis; Roberta Montanheiro Paolino; Roberto Fusco-Costa; Andressa Gatti; Danielle Oliveira Moreira; Paula Modenesi Ferreira; et al. (Mammal Research, 2022)

Synthesis, antibiotic modifying activity, ADMET study and molecular docking of chalcone (E)-3-(2,4-dichlorophenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one in strains of Staphylococcus aureus carrying MepA efflux pumps - Janaína Esmeraldo Rocha; Thiago Sampaio de Freitas; Jayze da Cunha Xavier; Raimundo Luiz Silva Pereira; Francisco Nascimento Pereira; Carlos Emídio Sampaio Nogueira; Márcia Machado Marinho; Paulo Nogueira Bandeira; Maria Alyce Albuquerque Fernandes; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos; et al. (Archives of Microbiology, 2022)

Dereplication and evaluation of the antinociceptive and anti-inflammatory activity of hydroethanolic extract of leaves from Campomanesia xanthocarpa O. Berg - Fabrício Damasceno Leandro; Layla Dutra Marinho Cabral; Tallita Marques Machado; Hector Henrique Ferreira Koolen; Felipe Moura Araújo da Silva; Fernanda Guilhon-Simplicio; Marcelo Aparecido da Silva; Alexandre Giusti-Paiva; Clarice de Carvalho Veloso Moura; Geraldo Alves da Silva (Natural Product Research, 2021)

Rumen fermentation and metabolic profile of rams fed with diets amended cottonseed cake - Fagton de Mattos Negrão; Anderson de Moura Zanine; Marinaldo Divino Ribeiro; Daniele de Jesus Ferreira; Alexandre Lima de Souza; Michelle de Oliveira Maia Parente; Henrique Nunes Parente; Rafael Henrique Pereira dos Reis; Túlio Otávio Jardim D.’Almeida Lins; Anny Graycy Vasconcelos de Oliveira Lima (Tropical Animal Health and Production, 2021)

Gonadal morphology and difference in reproductive development of two isolated populations of Astyanax rivularis ( T eleostei, C haracidae) - Patricia Postingel Quirino; Diógenes Henrique de Siqueira‐Silva; Maira da Silva Rodrigues; Amanda Pereira dos Santos‐Silva; Maria Luiza Ribeiro Delgado; José Augusto Senhorini; Alexandre Ninhaus‐Silveira; Rosicleire Veríssimo‐Silveira (Journal of Fish Biology, 2021)
Individuals of the same species may present different reproductive tactics depending on the environment in which they develop and mature. The present study aimed to define the gonadal development phases of males and females of Astyanax rivularis and to carry out a comparative analysis of the reproductive development of specimens captured in two isolated environments of the São Francisco River basin in Serra da Canastra, Brazil (Point 1: low vegetation and river showing calm and crystalline waters with small well formations; Point 2: current waters, and well‐established areas of arboreal vegetation). Thus, the gonads of A. rivularis specimens were collected, fixed and processed with techniques for light microscopy. Five maturation phases of the females' reproductive cycle were established: immature, developing, spawning capable, regressing and regenerating. Three maturation phases of the males' reproductive cycle were observed: spawning capable, regressing, and regenerating. There are differences in the phases of gonadal development of A. rivularis between the two sampling points so that, possibly, animals upstream of the waterfall demonstrate a delay in the reproductive cycle in relation to animals downstream.

Prediction of dry matter intake by meat sheep on tropical pastures - Antonio Leandro Chaves Gurgel; Gelson dos Santos Difante; João Virgínio Emerenciano Neto; Juliana Caroline Santos Santana; Patrick Bezerra Fernandes; Geraldo Tadeu dos Santos; Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Henrique Rocha de Medeiros (Tropical Animal Health and Production, 2021)

Anti-inflammatory actions of aspirin-triggered resolvin D1 (AT-RvD1) in bronchial epithelial cells infected with Cryptococcus neoformans - Bruno Sada Salerno; Aline Beatriz Mahler Pereira; Henrique Ismarsi de Souza; Mario Leon Silva-Vergara; Bruce David Levy; Alexandre Paula Rogerio (Inflammopharmacology, 2021)

Analysis of the Influence of Water Quality Parameters in the Final WQI Result Through Statistical Correlation Methods: Mirim Lagoon, RS, Brazil, Case Study - Marlon Heitor Kunst Valentini; Gabriel Borges dos Santos; Victória Huch Duarte; Henrique Sanchez Franz; Hugo Alexandre Soares Guedes; Rubia Flores Romani; Bruno Muller Vieira (Water, Air, & Soil Pollution, 2021)

Assessment of Natural and Post-Extraction Biomass from Acrocomia totai leaves: a Renewable Source of Energy - Gredson Keiff Souza; Alexandre Diório; Hugo Henrique Carline de Lima; Rogerio dos Santos Maniezzo; Andrelson Wellington Rinaldi; Nehemias Curvelo Pereira; Armando Mateus Pomini (BioEnergy Research, 2021)

Chemical composition and potentiating action of Norfloxacin mediated by the essential oil of Piper caldense C.D.C. against Staphylococcus aureus strains overexpressing efflux pump genes - Antonio Linkoln Alves Borges Leal; Camila Fonseca Bezerra; Camila Confortin; Luiz Everson da Silva; Emanuelle Machado Marinho; Márcia Machado Marinho; Mayron Alves Vasconcelos; Terezinha Gonçalves da Silva; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Henrique Douglas Melo Coutinho; Humberto Medeiros Barreto; et al. (Archives of Microbiology, 2021)

Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity - Edson Fiedler Abreu; Diego Marques Henriques Jung; Alexandre Uarth Christoff; Victor Hugo Valiati; Sharon A. Jansa; Alexandre Reis Percequillo (Systematics and Biodiversity, 2021)

How segregating populations of passion fruit react to CABMV infection? - Beatriz Murizini Carvalho; Alexandre Pio Viana; Flavia Alves da Silva; Pedro Henrique Dias dos Santos; Marcelo Eiras; Eileen Azevedo Santos (European Journal of Plant Pathology, 2021)

Natural intoxication caused by protodioscin in lambs kept in Brachiaria pastures - Marlova Cristina Mioto da Costa; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Gelson dos Santos Difante; Rafael Henrique de Tonissi Buschinelli de Goes; Eduardo de Souza Leal; Lucimara Modesto Nonato; Noemila Débora Kozerski; Gabriella Jorgetti de Moraes; Marcus Vinicius Garcia Niwa; Antonio Leandro Chaves Gurgel; et al. (Tropical Animal Health and Production, 2021)

The influence of increased water temperature on the duration of spermatogenesis in a neotropical fish, Astyanax altiparanae (Characiformes, Characidae) - Patricia Postingel Quirino; Maira da Silva Rodrigues; Elis Marina da Silva Cabral; Diógenes Henrique de Siqueira-Silva; Ricardo Hideo Mori; Arno Juliano Butzge; Rafael Henrique Nóbrega; Alexandre Ninhaus-Silveira; Rosicleire Veríssimo-Silveira (Fish Physiology and Biochemistry, 2021)

Preliminary study on testicular germ cell isolation and transplantation in an endangered endemic species Brycon orbignyanus (Characiformes: Characidae) - Diógenes Henrique de Siqueira-Silva; Amanda Pereira dos Santos Silva; Raphael da Silva Costa; José Augusto Senhorini; Alexandre Ninhaus-Silveira; Rosicleire Veríssimo-Silveira (Fish Physiology and Biochemistry, 2021)

New sources of melon accessions with resistance to bacterial fruit blotch at different phenological stages of melon growth and to multiple strains of Acidovorax citrulli - Emanuel Feitosa de Assunção; Claudeana Souza da Conceição; Elizabeth Rodrigues Alexandre; Marco Aurélio Siqueira da Gama; Glauber Henrique de Souza Nunes; Elineide Barbosa de Souza (Euphytica, 2021)

Genetic improvement of Capsicum frutescens: hybrid vigor for anthracnosis resistance and production traits - Ana Flávia Silva Amorim; Thiago Alexandre Santana Gilio; Janaina Barros de Jesus; Luiz Henrique Amorim de Souza; Isabela Vera dos Anjos; Kelly Lana Araujo; Marco Antonio Aparecido Barelli; Sandra da Costa Preisigke; Leonarda Grillo Neves (Euphytica, 2021)

Multivariate analysis to quantify genetic diversity and family selection in sour passion fruit under recurrent selection - Amanda Fernanda Nunes Ferreira; Willian Krause; Maria Helena Menezes Cordeiro; Alexandre Pio Viana; Eileen Azevedo Santos; Henrique Duarte Vieira (Euphytica, 2021)

The impact of El Niño Southern Oscillation on cropping season rainfall variability across Central Brazil - Alexandre Bryan Heinemann; Julian Ramirez‐Villegas; Luís Fernando Stone; Ana Paula Garcia Abreu Silva; David Henriques da Matta; Mario Ernesto Piscoya Diaz (International Journal of Climatology, 2021)
Local‐level understanding of within‐season rainfall variability and its relationship with the El Niño Southern Oscillation (ENSO) can shed light on crop yield variations and establish appropriate cropping calendars in rainfed systems. This requires information on the growing season, including its length, the total rainfall, the onset and cessation of rainfall, the number of wet and dry days, and the optimal sowing window. The objective of this study was to examine the onset and cessation of both the rainy and growing seasons using historical daily rainfall datasets (1980–2013) from 50 weather stations distributed across the main grain production region of Brazil. We then correlated the interannual variability of the climate variables and crop water availability with ENSO (using the Oceanic Niño Index, ONI). Across the study region, the onset of the rainy period ranged from late September to early November, and the cessation period ranged from late March to mid‐April. The onset of the growing season followed that of the rainy season, beginning across central and northern Mato Grosso in mid‐October, followed by Goiás and Tocantins, and finally Rondônia by the end of October. The length of the sowing window was reduced, and the mean optimal sowing date was delayed during La Niña years for most weather stations in the study region. Our results infer the need to adjust the cropping calendars for specific ENSO phases only in regions that conduct crop rotations. Based on rice crop model simulations of water availability, we propose a mean optimal crop sowing calendar for annual crops in Central Brazil. Highlights We analysed the impact of El Niño Southern Oscillation (ENSO) on the growing season characteristics of Central Brazil. The length of the sowing period is markedly reduced during La Niña years across the region. We propose a mean optimal crop sowing calendar for Central Brazil based on crop modelling results of ENSO effects.

Seasonality Effects on Antibacterial and Antibiotic Potentiating Activity against Multidrug-Resistant Strains of Escherichia coli and Staphylococcus aureus and ATR-FTIR Spectra of Essential Oils from Vitex gardneriana Leaves - Raimundo Luiz Silva Pereira; Thiago Sampaio de Freitas; Priscilla Ramos Freitas; Ana Carolina Justino de Araújo; Fábia Ferreira Campina; Kleber Ribeiro Fidelis; Jean Parcelli Costa do Vale; Antônio César Honorato Barreto; Henrique Douglas Melo Coutinho; Paulo Nogueira Bandeira; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos (Current Microbiology, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Soil fertility and fine root distribution after gypsum application in Eucalyptus plantations with different tolerance to water deficit - Yesid Alejandro Mariño Macana; Fábio Henrique Silva Floriano de Toledo; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves; Sandra Milena Díaz López; Camilo Andrés Barrero Cubillos; Ángela Nathalia Sierra Rojas; Hélder Andrade Bolognani (New Forests, 2020)

An overview of the transcriptional responses of two tolerant and susceptible sugarcane cultivars to borer (Diatraea saccharalis) infestation - Uilian Stefanello de Mello; Pedro Marcus Pereira Vidigal; Camilo Elber Vital; Adriano Cirino Tomaz; Milene de Figueiredo; Luiz Alexandre Peternelli; Márcio Henrique Pereira Barbosa (Functional & Integrative Genomics, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

A novel ZZ/ZW chromosome morphology type in Eigenmannia virescens (Gymnotiformes: Sternopygidae) from upper Paraná River basin - Carlos Alexandre Fernandes; Matheus Henrique Curiel; Leonardo Marcel Paiz; Lucas Baumgärtner; Diovani Piscor; Vladimir Pavan Margarido (Biologia, 2020)

Assisted phoresy of invertebrates by anurans in tank bromeliads: interspecific relationship - Alan Pedro de Araújo; Alexandre Henrique Carvalho Marques; Alexandre Pereira Dantas; Mauro de Melo Junior; Geraldo Jorge Barbosa de Moura; Moacir Santos Tinoco (Aquatic Sciences, 2020)

Mesquite pod meal as an additive increases milk total solids, lactose, fat and protein content in dairy cows - Luzyanne Varjão Aguiar; Herymá Giovane de Oliveira Silva; Sergio Augusto de Albuquerque Fernandes; Dirlane Novais Caires; Abias Santos Silva; Alexandre Etzberger Feistauer; Henrique Almeida da Silva; Lázaro Costa da Silva; Soraia Vanessa Matarazzo; Márcio dos Santos Pedreira (Tropical Animal Health and Production, 2020)

Aboveground biomass, transpiration and water use efficiency in eucalypt plantation fertilized with KCl, NaCl and phonolite rock powder - Fábio Henrique S. F. de Toledo; José Leonardo de Moraes Gonçalves; Yesid Alejandro Mariño; Alexandre de Vicente Ferraz; Eric Victor de Oliveira Ferreira; Gabriela Gonçalves Moreira; Rodrigo Hakamada; José Carlos de Arthur Júnior (New Forests, 2020)

Differential expression of the inflammasome complex genes in systemic lupus erythematosus - Heidi Lacerda Alves da Cruz; Catarina Addobbati Jordão Cavalcanti; Jaqueline de Azêvedo Silva; Camilla Albertina Dantas de Lima; Thiago Sotero Fragoso; Alexandre Domingues Barbosa; Andréa Tavares Dantas; Henrique de Ataíde Mariz; Angela Luzia Branco Pinto Duarte; Alessandra Pontillo; Sergio Crovella; Paula Sandrin-Garcia (Immunogenetics, 2020)

Antimicrobial activity and antibiotic synergy of a biphosphinic ruthenium complex against clinically relevant bacteria - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Francisco Vassiliepe de Sousa Arruda; Luiz Gonzaga do Nascimento Neto; José Marcos da Silveira Carvalho; Ana Claudia Silva Gondim; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2020)

Gradenigo’s syndrome in a woman with systemic lupus erythematosus - Bruno Bertoli Esmanhotto; Gabriela de Araújo; Alexandre da Silva Faco; Aline Pasqualli; James Henrique Yared (Acta Neurologica Belgica, 2020)

DNA-based species identification of shark finning seizures in Southwest Atlantic: implications for wildlife trade surveillance and law enforcement - Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Luis Henrique Fregadolli Ussami; Letícia Moraes; Carolina de Oliveira Magalhães; Alberto Ferreira de Amorim; Alexandre Wagner Silva Hilsdorf; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Biodiversity and Conservation, 2019)

First report of a genetic map and evidence of QTL for resistance to CABMV in a segregating population of Passiflora - Eileen Azevedo Santos; Alexandre Pio Viana; Fernando Henrique de Barros Walter; Josie Cloviane de Oliveira Freitas; Helaine Christine Cancela Ramos; Marcela Santana Bastos Boechat (European Journal of Plant Pathology, 2019)

Proteome of resistant and susceptible Passiflora species in the interaction with cowpea aphid-borne mosaic virus reveals distinct responses to pathogenesis - Beatriz Murizini Carvalho; Alexandre Pio Viana; Pedro Henrique Dias dos Santos; Andressa Leal Generoso; Caio Cezar Guedes Corrêa; Vanildo Silveira; Marcelo Eiras; Eileen Azevedo Santos (Euphytica, 2019)

Resistivity imaging for identification of fracture zones in crystalline bedrock in Brazil - Vagner Roberto Elis; Alexandre Bondioli; Andrea Teixeira Ustra; Ivan Mamede Carlos; Henrique Ângelo Piovezan Dal Pozzo (Sustainable Water Resources Management, 2019)

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

Spectral characterization and quantification of Phakopsora pachyrhizi urediniospores by Fourier transformed infrared with attenuated total reflectance - Lucas Henrique Fantin; Ana Lúcia de Souza Madureira Felício; Karla Braga; Giancarlo Michelino Gaeta; José Alexandre de França; Marcelo Giovanetti Canteri (European Journal of Plant Pathology, 2019)

Assimilation of Allochthonous Matter by Estuarine Consumers During the 2015 El Niño Event - Adna Ferreira Silva Garcia; Stéphanie Pasquaud; Henrique Cabral; Alexandre Miranda Garcia; Maurício Lang dos Santos; João Paes Vieira (Estuaries and Coasts, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Molecular genetic diversity in segregates of Vitis: implications for the breeding of grapevine aiming at resistance to Pratylenchus brachyurus - Paulo Ricardo dos Santos; Alexandre Pio Viana; Eileen Azevedo Santos; Fernando Henrique de Barros Walter; Summaira Riaz; Andrew Michael Walker (Euphytica, 2019)

Standard area diagrams to aid assessments of the severity of blight leaf spot symptoms on cassava leaves - Iris Carolina Henrique Lima Leite; Francisco Alberto Sousa Lima Filho; Rejane Livramento Freitas-Lopes; Sami Jorge Michereff; Alexandre Sandri Capucho; Ueder Pedro Lopes (Journal of Plant Pathology, 2019)

Accuracy and efficiency of assessments of cassava brown leaf spot aided by standard area diagram sets based on whole compound leaves or single central leaflets - Francisco Alberto Sousa Lima Filho; Íris Carolina Henrique Lima Leite; Alexandre Sandri Capucho; Sami Jorge Michereff; Rejane Livramento Freitas-Lopes; Ueder Pedro Lopes (European Journal of Plant Pathology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

A Standard Area Diagram Set to Aid Assessment of Ring Spot Severity in Sugarcane - Alexandre D. Roese; Henrique da S. S. Duarte (Sugar Tech, 2018)

Pulp and Paper Mill Effluent Treated by Combining Coagulation-Flocculation-Sedimentation and Fenton Processes - Mariana Grötzner; Emeline Melchiors; Luiz Henrique Schroeder; Alexandre Renato dos Santos; Kethlyn Ghellere Moscon; Marco Antonio de Andrade; Sérgio Henrique Saavedra Martinelli; Claudia Regina Xavier (Water, Air, & Soil Pollution, 2018)

Structural and functional characterization of a novel lipolytic enzyme from a Brazilian Cerrado soil metagenomic library - Paula Istvan; Amanda Araújo Souza; Aisel Valle Garay; Debora Farage Knupp dos Santos; Gideane Mendes de Oliveira; Renata Henrique Santana; Fabyano Alvares Cardoso Lopes; Sonia Maria de Freitas; João Alexandre Ribeiro Gonçalves Barbosa; Ricardo Henrique Krüger (Biotechnology Letters, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Patterns, biases and prospects in the distribution and diversity of Neotropical snakes - Thaís B. Guedes; Ricardo J. Sawaya; Alexander Zizka; Shawn Laffan; Søren Faurby; R. Alexander Pyron; Renato S. Bérnils; Martin Jansen; Paulo Passos; Ana L. C. Prudente; Diego F. Cisneros‐Heredia; Henrique B. Braz; et al. (Global Ecology and Biogeography, 2018)
Motivation We generated a novel database of Neotropical snakes (one of the world's richest herpetofauna) combining the most comprehensive, manually compiled distribution dataset with publicly available data. We assess, for the first time, the diversity patterns for all Neotropical snakes as well as sampling density and sampling biases. Main types of variables contained We compiled three databases of species occurrences: a dataset downloaded from the Global Biodiversity Information Facility (GBIF), a verified dataset built through taxonomic work and specialized literature, and a combined dataset comprising a cleaned version of the GBIF dataset merged with the verified dataset. Spatial location and grain Neotropics, Behrmann projection equivalent to 1° × 1°. Time period Specimens housed in museums during the last 150 years. Major taxa studied Squamata: Serpentes. Software format Geographical information system (GIS). Results The combined dataset provides the most comprehensive distribution database for Neotropical snakes to date. It contains 147,515 records for 886 species across 12 families, representing 74% of all species of snakes, spanning 27 countries in the Americas. Species richness and phylogenetic diversity show overall similar patterns. Amazonia is the least sampled Neotropical region, whereas most well‐sampled sites are located near large universities and scientific collections. We provide a list and updated maps of geographical distribution of all snake species surveyed. Main conclusions The biodiversity metrics of Neotropical snakes reflect patterns previously documented for other vertebrates, suggesting that similar factors may determine the diversity of both ectothermic and endothermic animals. We suggest conservation strategies for high‐diversity areas and sampling efforts be directed towards Amazonia and poorly known species.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Effects of fibre digestibility and level of roughage on performance and rumen fermentation of finishing beef cattle - Dannylo Oliveira Sousa; Bruno de Sousa Mesquita; Alexandre Vaz Pires; Miguel Henrique de Almeida Santana; Luis Felipe Prada Silva (Tropical Animal Health and Production, 2017)

Ants visiting extrafloral nectaries and pyrrolizidine alkaloids may shape how a specialist herbivore feeds on its host plants - Alexandre Eduardo Magalhães; Carlos Henrique Zanini Martins; Diomar Verçosa; Kamila Ferreira Massuda; José Roberto Trigo (Arthropod-Plant Interactions, 2017)

Response of Application of Growth Inhibitors on Sugarcane Productivity and Sucrose Accumulation in the Middle of Cropping Season in Brazil - Carlos Alexandre Costa Crusciol; Glauber Henrique Pereira Leite; Gabriela Ferraz de Siqueira; Marcelo de Almeida Silva (Sugar Tech, 2017)

Involvement of β adrenergic receptors in spasmolytic effect of caulerpine on guinea pig ileum - Luiz Henrique Agra Cavalcante-Silva; Ana Carolina de Carvalho Correia; Jéssica Celestino Ferreira Sousa; José Maria Barbosa-Filho; Bárbara Viviana de Oliveira Santos; George Emmanuel C. de Miranda; Magna Suzana Alexandre-Moreira; Fabiana de Andrade Cavalcante (Natural Product Research, 2016)

Antarctic strict anaerobic microbiota from Deschampsia antarctica vascular plants rhizosphere reveals high ecology and biotechnology relevance - Rafael José Marques Peixoto; Karla Rodrigues Miranda; Leandro Araujo Lobo; Alessandra Granato; Pedro de Carvalho Maalouf; Hugo Emiliano de Jesus; Caio T. C. C. Rachid; Saulo Roni Moraes; Henrique Fragoso dos Santos; Raquel Silva Peixoto; Alexandre Soares Rosado; Regina Maria Cavalcanti Pilotto Domingues (Extremophiles, 2016)

Non-linear Optical Responses of Low-Density Lipoprotein are Associated with Intima-Media Thickness of Carotid Artery in Athletes - Henrique Andrade R. Fonseca; Célia R. Bittencourt; Francisco A. Fonseca; Andrea M. Monteiro; Priscila R. Santos; Luciano Camargo; Luiz A. R. Costa; Alexandre Murad; Magnus Gidlund; Antonio M. Figueiredo-Neto; Maria Cristina O. Izar (Cell Biochemistry and Biophysics, 2016)

Selection strategy in families of energy cane based on biomass production and quality traits - Luís Cláudio Inácio da Silveira; Bruno Portela Brasileiro; Volmir Kist; Heroldo Weber; Edelclaiton Daros; Luiz Alexandre Peternelli; Márcio Henrique Pereira Barbosa (Euphytica, 2015)

Population structure and juvenile habitat use of dusky grouper (Epinephelus marginatus) in southern Brazil - Condini Mario; Tanner Susanne; Reis-Santos Patrick; Albuquerque Cristiano; Vieira João; Cabral Henrique; Garcia Alexandre (Frontiers in Marine Science, 2015)

Ecology and conservation of dusky grouper (Epinephelidae) in southern Brazil - Condini Mario; Vieira João; Cabral Henrique; Garcia Alexandre (Frontiers in Marine Science, 2015)

Process-based modelling of erosion, sediment transport and reservoir siltation in mesoscale semi-arid catchments - Axel Bronstert; José-Carlos de Araújo; Ramon J. Batalla; Alexandre Cunha Costa; José Miguel Delgado; Till Francke; Saskia Foerster; Andreas Guentner; José Andrés López-Tarazón; George Leite Mamede; Pedro Henrique Medeiros; Eva Mueller; et al. (Journal of Soils and Sediments, 2014)

Garcinielliptone FC, a polyisoprenylated benzophenone from Platonia insignis Mart., promotes vasorelaxant effect on rat mesenteric artery - Daniel Dias Rufino Arcanjo; Joaquim Soares da Costa-Júnior; Lucas Henrique Porfírio Moura; Alexandre Barros Falcão Ferraz; Raíssa Rebés Rossatto; Jorge Maurício David; Lucindo José Quintans-Júnior; Rita de Cássia Meneses Oliveira; Antônia Maria das Graças Lopes Citó; Aldeídia Pereira de Oliveira (Natural Product Research, 2014)

Global patterns of phylogenetic beta diversity components in bats - Franciele P. Peixoto; Pedro Henrique P. Braga; Marcus Vinicius Cianciaruso; José Alexandre F. Diniz‐Filho; Daniel Brito (Journal of Biogeography, 2014)
Aim To investigate global patterns of phylogenetic beta diversity (phylobetadiversity, PBD ) components in bats ( C hiroptera), testing whether the strong dispersal barriers among realms led to lineage differentiation between them and whether the flight capability of the study group created distance‐decay patterns in PBD , with lower turnover rates between the closest biogeographical regions. Location Global, delimited by biogeographical regions. Methods Using the global distribution of bats and a supertree available for most species, we calculated PBD using the complement of the PhyloSor index. In addition, to distinguish the relative roles of local (e.g. lineage filtering) and regional processes (e.g. speciation) in shaping broad‐scale patterns of PBD , we partitioned PBD into two components: the turnover component ( PBD Turn ) and the phylogenetic diversity ( PD ) component ( PBD PD ). We used a null model to test whether assemblages were more or less phylogenetically dissimilar than expected by chance. We also performed a M antel analysis to analyse the distance‐decay patterns of PBD and its two components. Results The most striking difference in PBD was found between the Old World and the New World. In general, the PBD pattern was determined by PBD Turn . For some adjacent regions we noticed the PBD PD component was more important, indicating that the dissimilarity was mostly due to differences in phylogenetic diversity. On the other hand, for other adjacent regions, the observed PBD Turn was higher than expected by chance and the PBD PD was lower. This demonstrates that, although these regions are relatively close in space, there are other factors driving phylogenetic differences between them (i.e. ecological factors). Main conclusions Our results suggest that at broad scales, the PBD of bats is determined by PBD Turn . We postulate that the flight ability of bats led to low turnover rates between adjacent regions in the absence of other factors that can drive differences between them (e.g. strong environmental barriers).

Antinociceptive and anti-inflammatory effects of flavonoids PMT1 and PMT2 isolated from Piper montealegreanum Yuncker (Piperaceae) in mice - Aline Cavalcanti de Queiroz; Harley da Silva Alves; Luiz Henrique Agra Cavalcante-Silva; Thays de Lima Matos Freire Dias; Mariana da Silva Santos; Gabriela Muniz de Albuquerque Melo; Eliane Aparecida Campesatto; Maria Célia de Oliveira Chaves; Magna Suzana Alexandre-Moreira (Natural Product Research, 2014)

Development and validation of a set of standard area diagrams to estimate severity of potato early blight - Henrique Silva Silveira Duarte; Laércio Zambolim; Alexandre Sandri Capucho; Antonio Fernandes Nogueira Júnior; André Wilson Campos Rosado; Carine Rezende Cardoso; Pierce Anderson Paul; Eduardo Seiti Gomide Mizubuti (European Journal of Plant Pathology, 2013)

Antinociceptive effect of 7-methoxyflavone isolated from Zornia brasiliensis - Anne Dayse Soares da Silva; Luiz Henrique Agra Cavalcante-Silva; Carolina B. Brito da Matta; Diego de Farias Silva; Morgana Vital de Araújo; Josean F. Tavares; Marcelo S. da Silva; Magna Suzana Alexandre-Moreira (Natural Product Research, 2013)

Analysing the effects of applying agricultural lime to soils by VNIR spectral sensing: a quantitative and quick method - Suzana Romeiro Araújo; José Alexandre Melo Demattê; Henrique Bellinaso (International Journal of Remote Sensing, 2013)

Heritability for resistance to Puccinia psidii Winter rust in Eucalyptus grandis Hill ex Maiden in Southwestern Brazil - Aline Cristina Miranda; Mario Luiz Teixeira de Moraes; Evandro Vagner Tambarussi; Edson Luis Furtado; Edson Seizo Mori; Paulo Henrique Muller da Silva; Alexandre Magno Sebbenn (Tree Genetics & Genomes, 2013)

NDP-MSH inhibits neutrophil migration through nicotinic and adrenergic receptors in experimental peritonitis - Jozi Figueiredo; Ana Elisa Ferreira; Rangel Leal Silva; Luis Ulloa; Paolo Grieco; Thiago Mattar Cunha; Sérgio Henrique Ferreira; Fernando de Queiróz Cunha; Alexandre Kanashiro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Isolation of microsatellite loci in the Amazon sailfin catfish Pterygoplichlhys pardalis (Castelneau, 1855) (Teleostei: Loricariidae) - Rosalina P. Pereira; Carlos Henrique dos A. dos Santos; Priscila Roberta M. Nascimento; Gisele T. Clímaco; Adna Cristina B. Sousa; Tatiana Campos; Alexandre Manoel K. Vergueiro-Júnior; Maria N. Paula-Silva; Vera Maria F. Almeida-Val (Conservation Genetics Resources, 2012)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Secondary metabolites isolated from Piper chimonantifolium and their antifungal activity - João Henrique G. Lago; Alexandre T. Ito; César M. Fernandes; Maria Claudia M. Young; Massuo J. Kato (Natural Product Research, 2012)

Repeatability of full-sib sugarcane families across harvests and the efficiency of early selection - Cássia Ângela Pedrozo; Márcio Henrique Pereira Barbosa; Felipe Lopes da Silva; Marcos Deon Vilela de Resende; Luiz Alexandre Peternelli (Euphytica, 2011)

Hemoglobin Regeneration Efficiency in Anemic Rats: Effects on Bone Mineral Composition and Biomechanical Properties - Alexandre Rodrigues Lobo; Eduardo Henrique Szpak Gaievski; Célia Colli (Biological Trace Element Research, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

Bioremediation of Mangroves Impacted by Petroleum - Henrique F. Santos; Flávia L. Carmo; Jorge E. S. Paes; Alexandre S. Rosado; Raquel S. Peixoto (Water, Air, & Soil Pollution, 2011)

Characterisation of the effect of a simulated hydrocarbon spill on diazotrophs in mangrove sediment mesocosm - Rodrigo Gouvêa Taketani; Henrique Fragoso dos Santos; Jan Dirk van Elsas; Alexandre Soares Rosado (Antonie van Leeuwenhoek, 2009)

Post-fire succession of small mammals in the Cerrado of central Brazil - Denis C. Briani; Alexandre R.T. Palma; Emerson M. Vieira; Raimundo P.B. Henriques (Biodiversity and Conservation, 2004)